Polymer composition for electrochemical device, conductive material composition, slurry composition, electrode film, and secondary battery

The use of a polymer composition with aliphatic hydrocarbon and nitrile group-containing units, along with an amide-based liquid medium, addresses the challenges of dispersibility and conductivity in secondary battery electrodes, resulting in improved battery performance and longevity.

JP7666579B1Active Publication Date: 2025-04-22TOYO INK MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023222006
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-04-22
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

Existing polymer compositions for electrochemical devices struggle to achieve optimal dispersibility and conductivity of conductive materials in secondary battery electrodes, leading to inadequate formation of the conductive network and subsequent deterioration of battery characteristics.

Method used

A polymer composition containing aliphatic hydrocarbon units and nitrile group-containing units with a strain-dependent loss tangent (tan δ) greater than 1, combined with an amide-based liquid medium, is used to enhance the dispersibility and conductivity of conductive materials in electrochemical devices.

Benefits of technology

The proposed polymer composition improves the initial dispersibility and maintains the shape of conductive materials, leading to enhanced conductivity and prolonged battery life, while also increasing the margin for formulation design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666579000001_ABST
    Figure 0007666579000001_ABST
Patent Text Reader

Abstract

The present invention provides a polymer composition for electrochemical devices, which can provide a conductive material composition having good dispersibility. [Solution] The polymer composition for electrochemical devices comprises a polymer containing an aliphatic hydrocarbon unit and a nitrile group-containing unit, and an amide-based liquid medium, wherein the polymer has a tan δ (loss tangent) of greater than 1 in a strain range of 0.01% to 10% in dynamic viscoelasticity measurement performed at a temperature of 100°C and a frequency of 10 Hz.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Embodiments of the present disclosure relate to a polymer composition for an electrochemical device, a conductive material composition, a slurry composition, an electrode film, and a secondary battery. [Background technology]

[0002] Lithium ion secondary batteries, which are representative of secondary batteries that are electrochemical elements, have characteristics such as small size and light weight, high energy density, and the ability to be repeatedly charged and discharged. Due to these characteristics, secondary batteries are used in a wide range of applications. In the field of secondary batteries, when carbon materials such as fine carbon nanotubes with excellent conductivity or carbon black with a well-developed structure are used as conductive materials for electrodes, particularly for positive electrodes with poor conductivity, in a well-dispersed state, it becomes easier to bring out the characteristics of the electrodes. Therefore, studies are being conducted to improve the characteristics of secondary batteries by dispersing conductive materials using dispersible polymers, etc.

[0003] As a technique for dispersing a conductive material well in a binder composition for secondary battery electrodes, Patent Document 1 describes a method for dispersing a conductive material having an alkylene structural unit and a nitrile group-containing monomer unit, which has a Mooney viscosity (ML 1+4 It has been disclosed that a copolymer (for example, hydrogenated nitrile rubber) having a modulus of elasticity (at 100° C.) of 40 or less is used as a binder composition for secondary battery electrodes. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2017 / 010093 Summary of the Invention [Problem to be solved by the invention]

[0005] The technology disclosed in Patent Document 1 aims to make the copolymer in the binder composition have a Mooney viscosity of 40 or less to facilitate adsorption of the copolymer to the surface of the conductive material, suppress aggregation of the conductive material, and improve dispersibility of the conductive material. On the other hand, the technology disclosed in Patent Document 1 aims to make the Mooney viscosity of the copolymer in the binder composition 5 or more to obtain adsorption stability of the copolymer to the conductive material and maintain dispersion stability of the conductive material.

[0006] However, in order to further improve the dispersibility of the conductive material, the development of a new polymer composition is desired from the aspect of more microscopic observation. In addition, if the conductive material is broken during dispersion treatment of the conductive material using the polymer composition, small pieces of the conductive material will be included in the electrode film, which may lead to insufficient formation of a conductive network and cause a deterioration in the battery characteristics of the secondary battery.

[0007] An object of the present disclosure is to provide a polymer composition for electrochemical elements that can provide a conductive material composition having good dispersibility, a conductive material composition containing the same, a slurry composition, an electrode film formed using the same, and a secondary battery. [Means for solving the problem]

[0008] The present inventors have conducted extensive research and found that the dispersibility of the conductive material in the dispersion can be obtained by using a polymer containing an aliphatic hydrocarbon unit and a nitrile group-containing unit, in which the tan δ (loss tangent) in the range of 0.01% to 10% strain is greater than 1 in dynamic viscoelasticity measurements performed at a temperature of 100° C. and a frequency of 10 Hz, and an amide-based liquid medium as the polymer composition for electrochemical elements. Furthermore, it has been found that the dispersibility of the conductive material in the dispersion and the conductivity in the electrode film can be compatible by using this polymer composition for electrochemical elements. Specifically, since the wetting promotion effect of the conductive material is strengthened in the dispersion, the viscosity increase in the dispersion treatment can be suppressed, and the initial dispersibility of the conductive material can be improved. Furthermore, the conductive material can be made highly concentrated in the dispersion. In addition, when the conductive material is dispersed using the polymer composition, the viscoelasticity of the dispersion can be appropriately controlled by the tan δ of the polymer, so that the conductive material is not broken during the dispersion treatment. As a result, not only is it possible to form a developed conductive network in the electrode film obtained using this dispersion, but the margin of formulation design can also be increased. This allows the conductive material to be uniformly distributed in the electrode film and maintain the shape of the conductive material, making it possible to provide an electrochemical element with high output, high capacity and long life.

[0009] That is, the present disclosure relates to the following embodiments, however, the embodiments of the present disclosure are not limited to the following.

[0010] [1] A polymer composition for electrochemical devices, comprising: a polymer containing an aliphatic hydrocarbon unit and a nitrile group-containing unit; and an amide-based liquid medium, wherein the polymer has a loss tangent (tan δ) of greater than 1 in a strain range of 0.01% to 10% in dynamic viscoelasticity measurements performed at a temperature of 100°C and a frequency of 10 Hz.

[0011] [2] The polymer composition for electrochemical devices according to [1], wherein, in a viscoelasticity measurement performed at a frequency of 10 Hz and a strain of 0.1%, the measurement temperature at which tan δ (loss tangent) = 1 is 80°C or lower when the temperature is increased at a rate of 10°C / min from 30°C to 110°C.

[0012] [3] The polymer composition for electrochemical devices according to [1] or [2], wherein a solution containing the polymer and N-methyl-2-pyrrolidone and having a solid content concentration of 20 mass % has a viscosity of less than 3000 mPa s at 25°C and 60 rpm when measured with a Brookfield viscometer. [4] The polymer composition for electrochemical elements according to any one of [1] to [3], wherein the content of the aliphatic hydrocarbon units is 50% by mass or more and 75% by mass or less, and the content of the nitrile group-containing units is 25% by mass or more and 50% by mass or less, based on the mass of the polymer. [5] The polymer composition for electrochemical devices according to any one of [1] to [4], wherein the Z-average molecular weight of the polymer is 10,000 or more and 250,000 or less.

[0013] [6] A conductive material composition comprising the polymer composition for electrochemical devices according to any one of [1] to [5] above, and a conductive material. [7] A slurry composition comprising the polymer composition for electrochemical devices according to any one of the above [1] to [5], a conductive material, and an active material. [8] An electrode film formed using a slurry composition containing the polymer composition for electrochemical devices according to any one of the above [1] to [5], a conductive material, and an active material. [9] A secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein at least one of the positive electrode and the negative electrode comprises an electrode film formed using a slurry composition containing the polymer composition for electrochemical elements according to any one of [1] to [5] above, a conductive material, and an active material. Effect of the Invention

[0014] According to the embodiments of the present disclosure, it is possible to provide a polymer composition for electrochemical devices capable of providing a conductive material composition having good dispersibility, a conductive material composition containing the same, a slurry composition, an electrode film formed using the same, and a secondary battery. [Brief description of the drawings]

[0015] [Figure 1]FIG. 1 shows a chart of tan δ (loss tangent) for evaluating the strain dependency of a polymer composition. [Diagram 2] FIG. 2 shows a chart of tan δ (loss tangent) for evaluating the temperature dependency of a polymer composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, as embodiments of the present disclosure, a polymer composition for electrochemical devices, a conductive material composition, a slurry composition, an electrode film, and a secondary battery will be described in detail. However, the present invention is not limited to the following embodiments, and the present invention also includes embodiments that are implemented within the scope of the present disclosure.

[0017] In this disclosure, carbon nanotubes may be referred to as "CNT" and carbon black as "CB". Acrylonitrile butadiene rubber may be referred to as "NBR" and hydrogenated acrylonitrile butadiene rubber may be referred to as "HNBR". In this disclosure, the polymer composition for electrochemical elements may be referred to simply as the polymer composition.

[0018] <Polymer> In one embodiment of the present disclosure, the polymer is a polymer containing at least an aliphatic hydrocarbon unit and a nitrile group-containing unit, and hereinafter, this polymer may be referred to as a nitrile-based polymer.

[0019] The aliphatic hydrocarbon unit is a unit containing an aliphatic hydrocarbon structure, and is preferably a unit consisting of only an aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure may be a saturated or unsaturated, substituted or unsubstituted, chain or cyclic aliphatic hydrocarbon structure. Preferably, the aliphatic hydrocarbon structure contains at least a saturated aliphatic hydrocarbon structure, and may further contain an unsaturated aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure preferably contains at least a linear aliphatic hydrocarbon structure, and may further contain a branched aliphatic hydrocarbon structure.

[0020] Examples of the aliphatic hydrocarbon unit include an alkylene unit, an alkenylene unit, an alkyl unit, an alkanetriyl unit, an alkanetetrayl unit, etc. The aliphatic hydrocarbon unit preferably contains at least an alkylene unit.

[0021] The alkylene unit is a unit containing an alkylene structure, and is preferably a unit consisting of only an alkylene structure. The alkylene structure is preferably a linear alkylene structure or a branched alkylene structure.

[0022] The alkylene unit preferably contains a unit represented by the following general formula (1A).

[0023] General formula (1A) [ka]

[0024] In general formula (1A), n represents an integer of 0 or greater than 1. n may be 1 to 20, 2 to 10, or 3 to 5. n is preferably an integer of 2 or greater, and more preferably an integer of 3 or greater. n is preferably an integer of 5 or less, and more preferably an integer of 4 or less. In particular, n is preferably 3.

[0025] The alkylene unit preferably contains a unit represented by the following general formula (1B).

[0026] General formula (1B) [ka]

[0027] In general formula (1B), n represents an integer of 1 or more. n may be 1 to 20, 2 to 10, or 2 to 4. n is preferably an integer of 4 or less, more preferably an integer of 3 or less, and even more preferably an integer of 2 or less. In particular, n is preferably 2.

[0028] The method for introducing an alkylene unit into a polymer is not particularly limited, but examples thereof include the following method (1a) or (1b).

[0029] In the method (1a), a polymer is produced by polymerization reaction using a monomer composition containing a conjugated diene monomer. The produced polymer contains monomer units derived from the conjugated diene monomer. In this disclosure, the "monomer units derived from the conjugated diene monomer" may be referred to as "conjugated diene monomer units", and the same may be omitted for monomer units derived from other monomers. Next, the conjugated diene monomer units are hydrogenated to convert at least a portion of the conjugated diene monomer units into alkylene units. In this disclosure, "hydrogenation" may be referred to as "hydrogenation". The finally obtained polymer contains units obtained by hydrogenating the conjugated diene monomer units as alkylene units.

[0030] The conjugated diene monomer unit includes at least a monomer unit having one carbon-carbon double bond. For example, the 1,3-butadiene monomer unit, which is a conjugated diene monomer unit, includes at least one monomer unit selected from the group consisting of a monomer unit having a cis-1,4 structure, a monomer unit having a trans-1,4 structure, and a monomer unit having a 1,2 structure, and may include two or more monomer units. The conjugated diene monomer unit may further include a monomer unit that does not have a carbon-carbon double bond and includes a branch point. In the present disclosure, the "branch point" refers to a branch point in a branched polymer, and when the conjugated diene monomer unit includes a monomer unit including a branch point, the above-prepared polymer is a branched polymer.

[0031] In the method (1b), a polymer is produced by a polymerization reaction using a monomer composition containing an α-olefin monomer. The produced polymer contains α-olefin monomer units. The final polymer contains the α-olefin monomer units as alkylene units.

[0032] Among these, the method (1a) is preferred because the polymer can be easily produced. The carbon number of the conjugated diene monomer is 4 or more, preferably 4 to 6. Examples of the conjugated diene monomer include conjugated diene compounds such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene. Among these, 1,3-butadiene is preferred. The alkylene unit preferably contains a unit obtained by hydrogenating a conjugated diene monomer unit (hydrogenated conjugated diene monomer unit), and more preferably contains a unit obtained by hydrogenating a 1,3-butadiene monomer unit (hydrogenated 1,3-butadiene monomer unit). The conjugated diene monomer can be used alone or in combination of two or more kinds.

[0033] The hydrogenation is preferably carried out by a method capable of selectively hydrogenating the conjugated diene monomer units. Examples of the hydrogenation method include known methods such as oil phase hydrogenation and aqueous phase hydrogenation.

[0034] The hydrogenation can be carried out by a conventional method. For example, the hydrogenation can be carried out by treating a polymer having conjugated diene monomer units dissolved in a suitable solvent with hydrogen gas in the presence of a hydrogenation catalyst. Examples of the hydrogenation catalyst include iron, nickel, palladium, rhodium, platinum, copper, and alloys and compounds thereof.

[0035] In the method (1b), the carbon number of the α-olefin monomer is 2 or more, preferably 3 or more, and more preferably 4 or more. The carbon number of the α-olefin monomer is preferably 6 or less, and more preferably 5 or less. Examples of the α-olefin monomer include α-olefin compounds such as ethylene, propylene, 1-butene, and 1-hexene. The α-olefin monomer may be used alone or in combination of two or more.

[0036] The alkylene unit preferably includes at least one selected from the group consisting of units having a linear alkylene structure and units having a branched alkylene structure, more preferably includes at least one selected from the group consisting of units consisting only of linear alkylene structures and units consisting only of branched alkylene structures, and further preferably includes at least one selected from the group consisting of units represented by the above formula (1B) and units represented by the above formula (1C).

[0037] In the aliphatic hydrocarbon unit, the content of the alkylene unit is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the total mass of the aliphatic hydrocarbon units (i.e., when the mass of the aliphatic hydrocarbon units is 100% by mass). The content of the alkylene unit is, based on the total mass of the aliphatic hydrocarbon units (i.e., when the mass of the aliphatic hydrocarbon units is 100% by mass), for example, less than 100% by mass, and may be 99.5% by mass or less, 99% by mass or less, or 98% by mass or less. The content of the alkylene unit may be 100% by mass.

[0038] The content of the aliphatic hydrocarbon unit is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, based on the mass of the polymer (i.e., when the mass of the polymer is 100% by mass). The content of the aliphatic hydrocarbon unit is preferably less than 85% by mass, more preferably 75% by mass or less, and even more preferably 70% by mass or less, based on the mass of the polymer (i.e., when the mass of the polymer is 100% by mass).

[0039] The nitrile group-containing unit is a unit containing a nitrile group, preferably a unit containing an alkylene structure substituted with a nitrile group, more preferably a unit consisting of only an alkylene structure substituted with a nitrile group. The alkylene structure is preferably a linear or branched alkylene structure. The nitrile group-containing unit may further contain a unit containing an alkyl structure substituted with a nitrile group, or a unit consisting of only an alkyl structure substituted with a nitrile group. The number of nitrile groups contained in the nitrile group-containing unit is preferably one.

[0040] The nitrile group-containing unit preferably contains a unit represented by the following general formula (2A).

[0041] General formula (2A) [ka]

[0042] In general formula (2A), n represents an integer of 2 or more. n may be 2 to 20, 2 to 10, or 2 to 6. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2.

[0043] The nitrile group-containing unit preferably contains a unit represented by the following general formula (2B).

[0044] General formula (2B) [ka]

[0045] In formula (2B), R represents a hydrogen atom or a methyl group, and is preferably a hydrogen atom.

[0046] The method of introducing the nitrile group-containing unit into the polymer is not particularly limited, but a method of preparing a polymer by polymerization reaction using a monomer composition containing a nitrile group-containing monomer (method (2a)) can be preferably used. The finally obtained polymer contains a unit derived from the nitrile group-containing monomer as a nitrile group-containing unit. As the nitrile group-containing monomer capable of forming the nitrile group-containing unit, a monomer containing a polymerizable carbon-carbon double bond and a nitrile group can be mentioned. For example, an α,β-ethylenically unsaturated group-containing compound having a nitrile group can be mentioned, and specifically, acrylonitrile, methacrylonitrile, etc. can be mentioned. In particular, from the viewpoint of increasing the intermolecular force between polymers and / or between a polymer and a dispersed substance (adsorbed substance), it is preferable that the nitrile group-containing monomer contains acrylonitrile. The nitrile group-containing monomer can be used alone or in combination of two or more kinds.

[0047] The content of the nitrile group-containing unit is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, based on the mass of the polymer (i.e., when the mass of the polymer is 100% by mass). The content of the nitrile group-containing unit is preferably 60% by mass or less, more preferably 55% by mass or less, even more preferably 50% by mass or less, and may be 40% by mass or less, based on the mass of the polymer (i.e., when the mass of the polymer is 100% by mass). By setting the content of the nitrile group-containing unit within the above range, the adsorption to the dispersed material and the affinity to the liquid medium can be controlled, and the dispersed material can be stably present in the liquid medium. In addition, the affinity of the polymer to the electrolyte can be controlled, and problems such as the polymer dissolving in the electrolyte in the battery and increasing the resistance of the electrolyte can be prevented. For example, the content of the nitrile group-containing units may be 10% by mass to 80% by mass, 20% by mass to 60% by mass, or 30% by mass to 40% by mass based on the mass of the polymer (i.e., when the mass of the polymer is 100% by mass). It is preferable that the total amount of the acrylonitrile group-containing units and the methacrylonitrile group-containing units satisfy these ranges, and it is more preferable that the acrylonitrile group-containing units satisfy these ranges.

[0048] In a preferred embodiment, the polymer has an aliphatic hydrocarbon unit content of 50% by mass to 75% by mass and a nitrile group-containing unit content of 25% by mass to 50% by mass, based on the mass of the polymer (i.e., when the mass of the polymer is 100% by mass). In a more preferred embodiment, the polymer contains alkylene units and nitrile group-containing units. It is more preferred that the polymer has an alkylene unit content of 50% by mass to 75% by mass and a nitrile group-containing unit content of 25% by mass to 50% by mass, based on the mass of the polymer (i.e., when the mass of the polymer is 100% by mass).

[0049] The polymer may further contain, as the aliphatic hydrocarbon unit, an alkenylene unit, an alkyl unit, a unit containing a branch point such as an alkanetriyl unit or an alkanetetrayl unit, etc. The unit containing a branch point is a unit different from a unit containing a branched alkylene structure and a unit containing a branched alkyl structure.

[0050] The alkenylene unit is a unit containing an alkenylene structure, and is preferably a unit consisting of only an alkenylene structure. The alkenylene structure is preferably a linear alkenylene structure or a branched alkenylene structure.

[0051] The alkenylene unit preferably includes at least one type selected from the group consisting of a unit including a linear alkenylene structure and a unit including a branched alkenylene structure, and more preferably includes at least one type selected from the group consisting of a unit consisting only of a linear alkenylene structure and a unit consisting only of a branched alkenylene structure.

[0052] For example, when a polymer is obtained through the above method (1a), a conjugated diene monomer unit having a carbon-carbon double bond therein may remain in the molecule of the polymer without being hydrogenated. The finally obtained polymer may contain a conjugated diene monomer unit having a carbon-carbon double bond therein as an alkenylene unit.

[0053] The alkyl unit is a unit containing an alkyl structure (however, it is a unit that does not fall under other aliphatic hydrocarbon units such as branched alkylene units, nitrile group-containing units, amide group-containing units, and carboxyl group-containing units), and is preferably a unit consisting of only an alkyl structure. The alkyl structure is preferably a linear alkyl structure or a branched alkyl structure.

[0054] The alkyl unit preferably includes at least one selected from the group consisting of units containing a linear alkyl structure and units containing a branched alkyl structure, and more preferably includes at least one selected from the group consisting of units consisting of only linear alkyl structures and units consisting of only branched alkyl structures. The number of carbon atoms in the alkyl unit may be 1 to 20, 2 to 10, 3 to 8, or 4 to 6. Examples of the alkyl unit include an n-butyl group, a sec-butyl group, a tert-butyl group, an isobutyl group, an n-pentyl group, an isopentyl group, a neopentyl group, an n-hexyl group, and an isohexyl group.

[0055] For example, when a polymer is obtained through the above method (1a) or (1b), it is preferable that at least a hydrogenated conjugated diene monomer unit or an α-olefin monomer unit is introduced as a terminal group of the polymer, and the finally obtained polymer may contain these monomer units as alkyl units.

[0056] The alkanetriyl unit is a unit containing an alkanetriyl structure, and is preferably a unit consisting only of an alkanetriyl structure.The alkanetetrayl unit is a unit containing an alkanetetrayl structure, and is preferably a unit consisting only of an alkanetetrayl structure.

[0057] For example, when a polymer is obtained through the above method (1a), the conjugated diene monomer unit may be introduced into the molecule as a monomer unit having a branch point and not having a carbon-carbon double bond in the unit. In this case, the finally obtained polymer is a branched polymer, and may contain the conjugated diene monomer unit as an aliphatic hydrocarbon unit having a branch point, such as an alkanetriyl unit or an alkanetetrayl unit. When the aliphatic hydrocarbon unit contains a unit having a branch point, the polymer is a branched polymer. The branched polymer may be a network polymer. A polymer containing a unit having a branch point can be three-dimensionally adsorbed to the dispersed material, and therefore can further improve dispersibility and stability.

[0058] The polymer may contain any unit, such as an amide group-containing unit or a carboxyl group-containing unit.

[0059] The amide group-containing unit is a unit containing an amide group, preferably a unit containing an alkylene structure substituted with an amide group, more preferably a unit consisting of only an alkylene structure substituted with an amide group. The alkylene structure is preferably a linear or branched alkylene structure. The amide group-containing unit may further contain a unit containing an alkyl structure substituted with an amide group, or a unit consisting of only an alkyl structure substituted with an amide group. The number of amide groups contained in the amide group-containing unit is preferably one.

[0060] In the present disclosure, the content of the unit can be determined by utilizing the amount of monomer used, NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurement.

[0061] The polymer in an embodiment of the present disclosure is characterized in that, in dynamic viscoelasticity measurement performed at a temperature of 100° C. and a frequency of 10 Hz, the polymer has a loss tangent tangent (tan δ) of greater than 1 in a strain range of 0.01% to 10%.

[0062] It has been found that the wettability of the polymer composition to the conductive material decreases when tan δ is in the range of 1 or less at a strain range of 0.01% to 10%. It is considered that when this tan δ is greater than 1, the wettability of the polymer composition to the conductive material is sufficient and the initial dispersibility can be improved.

[0063] While the dispersibility of the conductive material increases with the improvement of dispersion efficiency, excessive dispersion may cause breakage of the conductive material. It has been found that when tan δ is in the range of 1 or less at a strain range of 0.01% to 10%, excessive dispersion during dispersion treatment of the conductive material using the polymer composition is likely to cause breakage of the conductive material. When tan δ is in the range of more than 1, it is possible to control the dispersion treatment so that breakage of the conductive material does not occur due to the appropriate viscoelasticity of the dispersion. This is thought to enable the conductive material to have sufficient shape retention in the electrode film and improve the battery performance. For example, when a long conductive material such as carbon nanotubes is used as the dispersoid, breakage can be suppressed to obtain a dispersion with good dispersibility while maintaining the long shape. In addition, a conductive material composition in which carbon nanotubes or the like are dispersed using such a polymer can maintain its shape in the electrode film, and therefore can exhibit high conductivity.

[0064] Furthermore, when tan δ in the strain range of 0.01% to 10% is greater than 1, the polymer becomes viscous or fluid. A polymer to which viscosity or fluidity has been imparted can suppress an increase in the viscosity of the polymer solution. From this viewpoint as well, the initial dispersibility of the conductive material can be improved. Furthermore, the initial dispersibility can be maintained and long-term storage stability can be obtained.

[0065] In dynamic viscoelasticity measurement at a temperature of 100° C. and a frequency of 10 Hz, the polymer preferably has a loss tangent tan δ (tan δ) in the strain range of 0.01% to 10% of greater than 1, but may be 1 to 100, 1 to 50, 1 to 10, or 1 to 5. In the present disclosure, it has been found that the strain range of 0.01% to 10% in the measurement of tan δ (loss tangent) is a factor that affects the adsorption of the copolymer to the conductive material, the solubility of the copolymer, the viscosity and viscosities of the copolymer, etc. in the polymer composition. By controlling the tan δ (loss tangent) of the copolymer to be greater than 1 in the entire strain range of 0.01% to 10%, it is possible to contribute to improving the dispersibility of the conductive material in the polymer composition and improving the shape retention of the conductive material. Due to these characteristics, the polymer can be used as a dispersant in the conductive material composition.

[0066] When the polymer composition according to the embodiment of the present disclosure is used, the effect can be exhibited in both media dispersion and media-less dispersion. In media dispersion, the tan δ (loss tangent) of the polymer is appropriately controlled, so that during the dispersion process of adding a conductive material to the polymer composition, the collision efficiency of the dispersion media is improved, and the breakage of the conductive material can be suppressed by the appropriate viscoelasticity of the dispersion. In media-less dispersion, the tan δ (loss tangent) of the polymer is appropriately controlled, so that during the dispersion process of adding a conductive material to the polymer composition, the shear stress can be applied uniformly and sufficiently to the dispersion, so that the dispersion efficiency is improved, and the breakage of the conductive material can be suppressed by the appropriate viscoelasticity of the dispersion.

[0067] In a polymer according to an embodiment of the present disclosure, in a viscoelasticity measurement performed at a frequency of 10 Hz and a strain of 0.1%, when the temperature is increased at a rate of 10° C. / min from 30° C. to 110° C., the measurement temperature at which tan δ (loss tangent) = 1 is preferably 80° C. or lower. Hereinafter, the measurement temperature at which tan δ (loss tangent) = 1 is also referred to as the measurement temperature (tan δ = 1). The polymer may have a measurement temperature (tan δ=1) of less than 110° C. or 100° C. or less, preferably 80° C. or less, 70° C. or less, 60° C. or less, 50° C. or less, 40° C. or less, or 30° C. or less. This measurement temperature (tan δ=1) may be such that tan δ is greater than 1 over the entire temperature range of 30 to 110° C.

[0068] By setting the measurement temperature (tan δ=1) at 80° C. or lower, the initial dispersibility can be improved under normal temperature conditions in the environment in which the conductive material is dispersed as a dispersoid in the polymer composition. In addition, since the polymer composition can maintain the adsorption of the polymer to the conductive material, the long-term storage stability can be improved. In addition, during the dispersion treatment of the conductive material using the polymer composition, even if excessive dispersion is performed due to the improvement in dispersion efficiency, breakage of the conductive material can be suppressed, and a conductive material composition that maintains the shape of the conductive material can be obtained. From this viewpoint, the measurement temperature (tan δ=1) is preferably 30° C. or higher and 110° C. or lower, more preferably 30° C. or higher and 80° C. or lower, and even more preferably 40° C. or higher and 80° C. or lower.

[0069] The tan δ of a polymer is calculated by the following formula 1 and is measured by dynamic viscoelasticity measurement. tan δ = loss modulus (G'') / storage modulus (G') Equation 1

[0070] Concerning the strain dependency of a polymer, tan δ can be measured using a viscoelasticity measuring device (for example, MCR302e (Anton Paar)). Specifically, using parallel plates with a diameter of 25 mm, the GAP is set to the thickness of the sample, and the measurement is performed under the conditions of a temperature of 100°C, a frequency of 10 Hz, and a strain range of 0.01 to 10%. It is determined whether tan δ is greater than 1 in the strain range of 0.01 to 10%.

[0071] Regarding the temperature dependence of a polymer, tan δ can be measured using a viscoelasticity measuring device (for example, MCR302e (Anton Paar)). Specifically, using parallel plates with a diameter of 25 mm, measurements are performed under the following conditions: a constant normal force of 100 mN, a frequency of 10 Hz, a strain of 0.1%, a temperature range of 30°C to 110°C, and a heating rate of 10°C / min. The temperature at which tan δ=1 is obtained within the temperature range of 30°C to 110°C.

[0072] The polymer sample to be subjected to the dynamic viscoelasticity measurement is obtained by dropping the polymer solution onto a fluororesin mold and drying to remove the solvent. In the case of a viscous polymer, it is used after being cooled with liquid nitrogen and solidified, and then removed from the fluororesin mold. In detail, the tan δ in the strain range of 0.01 to 10% and the measurement temperature (tan δ = 1) can be measured according to the method described in the examples.

[0073] The method for controlling the tan δ of the nitrile polymer is not particularly limited. For example, the tan δ can be controlled by changing the composition (structural unit type, content, hydrogenation rate, etc.), structure (linearity rate, etc.), molecular weight, preparation conditions (polymerization temperature, amount of molecular weight modifier, etc.) of the nitrile polymer. For example, the tan δ of the nitrile polymer can be controlled by the following method.

[0074] In the control method a, tan δ is increased by increasing the amount of molecular weight modifier used in the production of the polymer. In the control method b, a base is added to modify the nitrile groups contained in the nitrile group-containing structural units of the polymer, for example by hydrolysis, thereby increasing the tan δ of the polymer. In control method c, tan δ is increased by applying mechanical shear stress to the polymer.

[0075] In the control method b, a base may be added when preparing a polymer containing an aliphatic hydrocarbon unit and a nitrile group-containing unit. Alternatively, a polymer containing an aliphatic hydrocarbon unit and a nitrile group-containing unit that has already been prepared may be dissolved in a solvent capable of dissolving the polymer, and then a base may be added to the polymer to adjust the tan δ. The base to be added may be at least one selected from the group consisting of inorganic bases and organic hydroxides (organic bases). When preparing the polymer by adding a base, tan δ can be increased in a shorter time by applying heat to an extent that does not cause the solvent to ignite or boil.

[0076] Examples of inorganic bases include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, borates, or alkoxides of alkali metals or alkaline earth metals; and ammonium hydroxide, etc. Among these, hydroxides or alkoxides of alkali metals or alkaline earth metals are preferred from the viewpoint of easy supply of cations. Examples of the hydroxide of an alkali metal include lithium hydroxide, sodium hydroxide, and potassium hydroxide. Examples of the alkoxide of an alkali metal include lithium methoxide, lithium ethoxide, lithium propoxide, lithium t-butoxide, lithium n-butoxide, sodium methoxide, sodium ethoxide, sodium propoxide, sodium t-butoxide, sodium n-butoxide, potassium methoxide, potassium ethoxide, potassium propoxide, potassium t-butoxide, and potassium n-butoxide. Examples of the hydroxide of an alkaline earth metal include calcium hydroxide and magnesium hydroxide. Among these, it is more preferable to use at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, potassium hydroxide, and sodium t-butoxide, and sodium hydroxide is more preferable. The metal contained in the inorganic base may be a transition metal.

[0077] The organic hydroxide is a salt containing an organic cation and a hydroxide ion. Examples of the organic hydroxide include trimethyl-2-hydroxyethyl ammonium hydroxide, tetramethyl ammonium hydroxide, cetyl trimethyl ammonium hydroxide, hexadecyl trimethyl ammonium hydroxide, trimethyl phenyl ammonium hydroxide, 3-trifluoromethyl-phenyl trimethyl ammonium hydroxide, and benzyl trimethyl ammonium hydroxide. Among these, it is particularly preferable to use at least one selected from the group consisting of trimethyl-2-hydroxyethyl ammonium hydroxide and tetramethyl ammonium hydroxide.

[0078] As the base, an alkanolamine may be used, such as monoethanolamine, diethanolamine, triethanolamine, monoisopropanolamine, diisopropanolamine, triisopropanolamine, methylethanolamine, or methyldiethanolamine.

[0079] The amount of the base used is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on the mass of the nitrile polymer. The amount of the base used is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the mass of the nitrile polymer. These ranges are preferable for controlling the tan δ of the nitrile polymer.

[0080] In the control method b, the increase in tan δ can be achieved by mixing a polymer containing an aliphatic hydrocarbon unit and a nitrile group-containing unit, a base, and a liquid medium. Any other component may be mixed. There is no limitation on the order of addition of the polymer, base, and liquid medium to the container and the mixing method, and they may be added to the container at the same time; the polymer, base, and liquid medium may be added separately to the container; or one or both of the polymer and the base may be mixed with the liquid medium to prepare a polymer-containing liquid and / or a base-containing liquid, and the polymer-containing liquid and / or the base-containing liquid may be added to the container. In particular, since the nitrile group can be efficiently modified, a method in which a base dispersion in which a base is dispersed in a liquid medium is added to a polymer solution in which a polymer is dissolved in a liquid medium while stirring is preferred. A disperser (dispersing machine) or a homogenizer can be used for stirring. As the liquid medium, a liquid medium that can be used for the polymer composition described later can be used.

[0081] There is no limit to the temperature during mixing, but the denaturation can be accelerated by heating to 30°C or higher. In addition, a small amount of water and / or alcohol may be added to the container to promote the denaturation of the nitrile polymer. Water and / or alcohol may be added to the container while mixing the polymer and the base, before adding the nitrile polymer and the base to the container, or may be added to the container simultaneously with or subsequent to the nitrile polymer and the base. In addition, when the nitrile polymer, the base, and any optional components used as necessary are highly hygroscopic, water may be contained as absorbed water. The amount of water and / or alcohol is preferably 0.05 to 20% by mass, more preferably 0.05 to 5% by mass, and even more preferably 0.05 to 1% by mass, based on the mass of the nitrile polymer.

[0082] Examples of alcohols include methanol, ethanol, propanol, isopropanol, butanol, isobutanol, secondary butanol, tertiary butanol, benzyl alcohol, ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, butylene glycol, hexanediol, pentanediol, glycerin, hexanetriol, and thiodiglycol. The alcohols can be used alone or in combination of two or more. The hydrolysis is preferably carried out in the presence of at least one selected from the group consisting of methanol, ethanol, butanol, hexanol, and water, and is particularly preferably carried out in the presence of water.

[0083] The control method c may be carried out by applying mechanical shear stress when preparing a polymer containing an aliphatic hydrocarbon unit and a nitrile group-containing unit, or by dissolving an already prepared polymer containing an aliphatic hydrocarbon unit and a nitrile group-containing unit in a liquid medium capable of dissolving the polymer and then applying mechanical shear stress. Tan δ can also be controlled by applying mechanical shear stress to the polymer before dissolution using a roll or kneader, but it is more preferable to apply shear stress to the polymer solution, since it is more efficient to use the nitrile polymer as a dispersant in a liquid medium capable of dissolving the polymer.

[0084] Examples of the method of applying shear stress to a polymer solution include a method using a dispersing means such as a homogenizer or a Silverson mixer. Although shear stress can be applied using a disperser or the like, it is preferable to use a dispersing means capable of applying a higher shear stress such as a homogenizer or a Silverson mixer. Examples of the method of applying mechanical shear stress to a polymer before dissolution include a method using a dispersing means such as a kneader or a two-roll mill.

[0085] The polymer in an embodiment of the present disclosure preferably contains a polymer and N-methyl-2-pyrrolidone, and when a solution having a solid content concentration of 20 mass % is measured with a Brookfield viscometer, the viscosity at 25°C and 60 rpm is less than 3000 mPa s. The polymer according to one embodiment has an improved initial dispersibility due to a tan δ of more than 1 in the strain range of 0.01 to 10%, and therefore the viscosity of the polymer solution can be reduced. Even when the polymer content is high, the viscosity of the polymer solution can be reduced. By using a polymer having such viscosity properties, the viscosity of the polymer composition and the conductive material composition can be reduced. When measured with a Brookfield viscometer at 25° C. and 60 rpm, the viscosity of the polymer solution may be less than 3000 mPa·s, less than 1000 mPa·s, or less than 500 mPa·s. For example, the viscosity of the polymer solution may be 10 mPa·s to 3000 mPa·s, or 100 mPa·s to 1000 mPa·s.

[0086] The viscosity of the polymer solution is a value measured by leaving the polymer solution in a thermostatic chamber at 25° C. for at least 1 hour and then measuring the viscosity with a B-type viscometer at a rotor rotation speed of 60 rpm. More specifically, the viscosity can be measured according to the method in the Examples.

[0087] The polymer in the embodiment of the present disclosure preferably has a Z-average molecular weight of 10,000 or more and 250,000 or less. A polymer specified by the Z-average molecular weight has a controlled molecular distribution on the high molecular weight side. When the Z-average molecular weight is 250,000 or less, the proportion of high molecular weight molecular distribution is low, and the polymer has viscosity and fluidity, which improves the wettability of the conductive material when used as a dispersoid, and can further increase the initial dispersibility. In particular, it is effective in improving the wettability of the conductive material, which is a carbon material. Also, when the Z-average molecular weight is 10,000 or more, it is possible to maintain adsorption to the conductive material in the conductive material composition and maintain dispersibility. For example, the Z-average molecular weight of the polymer may be 10,000 to 250,000, 10,000 to 200,000, 20,000 to 150,000, 30,000 to 100,000, 30,000 to 60,000, or 30,000 to 50,000. By being within the above range, when a conductive material composition is prepared using the polymer, both initial dispersibility and storage stability can be achieved.

[0088] The polymer in the embodiment of the present disclosure may have a weight average molecular weight (Mw) of 5,000 to 100,000, 10,000 to 70,000, or 20,000 to 50,000. Within these ranges, the effects of improving the wettability of the conductive material, particularly the carbon material, and suppressing aggregation can be obtained, and the storage stability of the polymer composition can be further improved.

[0089] In the present disclosure, the Z-average molecular weight and the weight-average molecular weight are measured by gel permeation chromatography (GPC) equipped with an RI detector using a molecular weight measurement sample. In detail, they can be measured according to the method in the examples. The Z-average molecular weight and the weight-average molecular weight are each polystyrene equivalent values.

[0090] A measurement sample for measuring the molecular weight of the polymer contained in the polymer composition is prepared by the following method. The polymer composition is dropped into purified water to precipitate the polymer, and the precipitate is collected. The precipitate is dissolved in tetrahydrofuran (THF) to obtain a solution. This solution is washed with purified water, and the purified precipitate is redissolved in THF to obtain a measurement sample. In detail, a measurement sample can be prepared according to the method of the examples, and the molecular weight can be measured.

[0091] The wettability of the polymer to the conductive material can be evaluated from the ratio of the solid content of the supernatant to the solid content of the bottom after preparing a dispersion of the polymer, the conductive material, and the liquid medium and leaving it to stand for 24 hours. Specifically, a polymer solution of N-methyl-2-pyrrolidone (NMP) containing 8% by mass of the polymer is prepared. A conductive material is added to this polymer solution to prepare a polymer dispersion containing 2% by mass of the conductive material. This polymer dispersion is left to stand for 1 hour without stirring, and after leaving it to stand for 1 hour, measurement samples are taken from the supernatant and the bottom. The wettability of the polymer to the conductive material can be evaluated from the mass ratio of (solid content contained in the supernatant) / (solid content contained in the bottom). This mass ratio is preferably 0.5 or more and less than 1.5, and more preferably 0.75 or more and less than 1.25. This mass ratio is determined by using carbon nanotubes JENOTUBE10B (average outer diameter 10 nm, BET specific surface area 230 m) as the conductive material. 2 / g, multi-walled CNT) can be used to relatively evaluate the wettability of the polymer. For details, it can be evaluated according to the method in the Examples.

[0092] <Liquid medium> In the polymer composition, the liquid medium is not particularly limited as long as it is miscible with the polymer. In the present disclosure, "miscible with the polymer" means that when 0.5 g of the polymer is dissolved in 100 g of the liquid medium at 25°C, the insoluble content is 10 mass% or less. The insoluble content can be calculated by filtering the undissolved polymer and the solution to recover the undissolved polymer, drying the recovered polymer with hot air, and measuring the mass. The liquid medium is preferably capable of dissolving the polymer, and more preferably is a high dielectric constant solvent capable of dissolving the polymer. In the present disclosure, "capable of dissolving the polymer" means that when 0.5 g of the polymer is dissolved in 100 g of the liquid medium at 25°C, no insoluble matter can be visually confirmed and the solution is clear and transparent. When a liquid medium capable of dissolving the polymer is used, a good dispersion state can be easily obtained when a conductive material is added.

[0093] In one embodiment, the liquid medium preferably contains a solvent consisting of any one of the high dielectric constant solvents, or a mixed solvent consisting of two or more of them. In addition, one or more other solvents may be mixed with the high dielectric constant solvent. In the present disclosure, the "high dielectric constant solvent" is a solvent having a relative dielectric constant value described in the Solvent Handbook or the like of 2.5 or more at 20°C, more preferably 25 or more. When a conductive material composition is prepared using a high dielectric constant solvent as the liquid medium, the interaction between the nitrile group contained in the polymer of the above embodiment, the conductive material, and the liquid medium can be enhanced. From the viewpoint of the solubility of the polymer, the relative dielectric constant of the high dielectric constant solvent is preferably 60 or less at 20°C, more preferably 50 or less. In one embodiment, the relative dielectric constant of the high dielectric constant solvent may be preferably 30 to 50.

[0094] In one embodiment, the liquid medium is preferably a non-aqueous liquid medium. The polymer of the above embodiment tends to have low solubility in water. Therefore, when water is present in the conductive material composition, it tends to be difficult to obtain a desired good dispersion state. Therefore, it is preferable that the liquid medium does not substantially contain water. "Substantially does not contain" means that water is not intentionally added in an amount exceeding the amount contained due to moisture absorption or the like. The water content based on the total mass of the liquid medium is preferably 5 mass% or less, more preferably 1 mass% or less, and even more preferably 0.5 mass% or less. Even if the conductive material composition is prepared without adding water, the conductive material composition may contain about 0.1 mass% water due to moisture absorption or the like. From the above viewpoint, the liquid medium is preferably an organic solvent, and more preferably a polar organic solvent that does not donate protons.

[0095] In the polymer composition, when a polymer containing an aliphatic hydrocarbon unit and a nitrile group-containing unit is used, it is preferable to use an amide-based liquid medium. The amide-based liquid medium has excellent solubility for the polymer. In addition, the amide-based liquid medium is a high-dielectric constant solvent, which can enhance the interaction with the polymer and contribute to improving the initial dispersibility. In addition, the amide-based liquid medium is a polar organic solvent that does not donate protons, which can contribute to the stability over time of the polymer, as well as the conductive material and binder resin.

[0096] Examples of amide-based liquid media include N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc. Among them, from the viewpoint of excellent polymer solubility, high dielectric constant, etc., it is preferable to use at least one of N-methyl-2-pyrrolidone (NMP) and N-ethyl-2-pyrrolidone (NEP), more preferably to use N-methyl-2-pyrrolidone (NMP) alone, and it is also preferable to use N-methyl-2-pyrrolidone (NMP) in combination with other liquid media.

[0097] Further examples of the liquid medium include polar organic solvents that do not donate protons, such as heterocyclic, sulfoxide, sulfone, lower ketone, and carbonate liquid media. More specifically, the following can be mentioned.

[0098] Heterocyclic: cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc. Sulfoxides: dimethyl sulfoxide, etc. Sulfone series: hexamethylphosphorotriamide, sulfolane, etc. Lower ketones: acetone, methyl ethyl ketone, etc. Carbonates: diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate, etc. Others: Tetrahydrofuran, acetonitrile, etc.

[0099] <Polymer Composition> The polymer composition for electrochemical devices according to one embodiment of the present disclosure includes a polymer and an amide-based liquid medium. The polymer includes an aliphatic hydrocarbon unit and a nitrile group-containing unit, and the details are as described above. The details of the amide-based liquid medium are as described above.

[0100] In the polymer composition, the nitrile polymer may be 1 to 50, 2 to 40, or 5 to 30% by mass based on the total mass of the polymer composition. Even when the polymer composition is contained at a high concentration of 20% by mass or more, the tan δ in the strain range of 0.01% to 10% is greater than 1, so that a dispersion can be provided that has dispersibility of the conductive material, suppresses breakage of the conductive material during dispersion treatment, and maintains the shape of the conductive material. In the polymer composition, the nitrile polymer may be 50 to 100 mass %, 75 to 100 mass %, or 80 to 99.8 mass % based on the total solid content. The polymer composition may contain other polymers in addition to the nitrile polymer. In the polymer composition, the other polymer may be 0 to 100 parts by mass, 0.1 to 50 parts by mass, or 1 to 10 parts by mass, based on 100 parts by mass of the nitrile polymer. The polymer composition may not contain other polymers.

[0101] In the polymer composition, the amide liquid medium may be 50 to 99 mass %, 60 to 98 mass %, or 70 to 95 mass % based on the total mass of the polymer composition. The polymer composition may contain other liquid media in addition to the amide liquid medium. In the polymer composition, the other liquid medium may be 0 to 100 parts by mass, 0.1 to 50 parts by mass, or 1 to 10 parts by mass relative to 100 parts by mass of the amide liquid medium. The polymer composition may not contain other liquid media. When dispersing a conductive material using the polymer composition, by using a nitrile polymer as the main component, more preferably by using only a nitrile polymer, the viscoelasticity of the polymer composition can be appropriately controlled and breakage of the conductive material during dispersion treatment can be further suppressed.

[0102] The solid content of the polymer composition may be 1 to 60% by mass, 2 to 50% by mass, or 5 to 35% by mass. The solid content of the polymer composition may be appropriately set according to the molecular structure of the polymer, the characteristics such as the type of liquid medium, the use of the polymer composition, the type of conductive material to be dispersed, and the like. In the present disclosure, the solid content is the total amount of components excluding the liquid medium. Specifically, the polymer composition is thoroughly dried in an oven set at a temperature equal to or higher than the temperature at which the liquid medium can evaporate to leave only the solid content, and the solid content mass of the polymer composition is measured, and the solid content is calculated by dividing the measured value by the total mass of the polymer composition.

[0103] The polymer composition may contain an additional optional component as necessary. For example, the polymer composition may contain a base. The base may be a component that can be contained in the raw material of the nitrile polymer, a component that is mixed in from the synthetic raw material of the nitrile polymer, etc., and the details are as described above.

[0104] The polymer composition means a composition that does not contain a conductive material and an active material. In the polymer composition, the conductive component may be 5% by mass or less, 1% by mass or less, or 0.1% by mass or less, and the conductive component may not be substantially contained. In the polymer composition, the active material may be 5% by mass or less, 1% by mass or less, or 0.1% by mass or less, and the active material may not be substantially contained.

[0105] <Conductive composition> The conductive material composition according to one embodiment of the present disclosure includes a polymer composition for electrochemical devices and a conductive material. The details of the polymer composition for electrochemical devices are as described above. The conductive material will be described below.

[0106] <Conductive material> The conductive material is not particularly limited, but is preferably a carbon material. Examples of conductive carbon materials include graphite, carbon black, graphene, multilayer graphene, fullerene, carbon nanotubes, carbon nanofibers, and other fibrous carbon materials. These may be used alone or in combination of two or more. Examples of graphite include artificial graphite, flake graphite, lump graphite, and natural graphite such as amorphous graphite.

[0107] The carbon material plays a role in forming a conductive path inside the electrode, and from the viewpoint of being required to be less likely to be cut due to expansion and contraction of the electrode film, it is preferable to include a fibrous carbon material, and more preferably to be a fibrous carbon material. From the viewpoint of conductivity, ease of availability, and cost, it is preferable to use carbon black and / or carbon nanotubes. In addition, from the viewpoint of reducing raw material costs and efficiently forming a conductive network, two or more types of the same type of carbon material having different physical properties may be used in combination. Examples of the same type of carbon material having different physical properties include two or more types of carbon nanotubes having different average outer diameters or average fiber diameters, or two or more types of carbon black having different specific surface areas.

[0108] The carbon purity of a carbon material is expressed as the content (mass%) of carbon atoms in the carbon material. The higher the carbon purity, the more preferable it is, and it is preferably 90 mass% or more, more preferably 95 mass% or more, even more preferably 98 mass% or more, and particularly preferably 99 mass% or more, relative to 100 mass% of the carbon material. By keeping the carbon purity within the above range, it is possible to prevent problems such as short circuits caused by the formation of dendrites due to impurities such as metals.

[0109] <Carbon nanotubes> Carbon nanotubes are formed by rolling planar graphite into a cylindrical shape, and include single-walled carbon nanotubes and multi-walled carbon nanotubes, or may be a mixture of these. Single-walled carbon nanotubes have a structure in which one layer of graphite is rolled. Multi-walled carbon nanotubes have a structure in which two or more layers of graphite are rolled. In addition, the sidewall of the carbon nanotube does not have to have a graphite structure. The carbon nanotube may be, for example, a carbon nanotube having a sidewall with an amorphous structure.

[0110] The shape of the carbon nanotube is not limited. The shape of the carbon nanotube may be various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stack type), trump-like (platelet), and coil-like. Among them, the shape of the carbon nanotube in this embodiment is preferably needle-like or cylindrical tube-like. The carbon nanotube may be a single shape or a combination of two or more shapes.

[0111] Examples of the form of carbon nanotubes include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. Carbon nanotubes may have any one of these forms or a combination of two or more of these forms.

[0112] The average outer diameter of the carbon nanotubes is preferably 1 nm or more, more preferably 3 nm or more, and even more preferably 5 nm or more. The average outer diameter of the carbon nanotubes is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 13 nm or less. When the average outer diameter is within the above range, when applied to a secondary battery, a good conductive network is easily formed in the electrode, and the active material inside the secondary battery can be utilized evenly during charging and discharging, thereby suppressing deterioration of the active material and further improving the cycle characteristics of the secondary battery. The average outer diameter of the carbon nanotubes can be calculated by observing and photographing the carbon nanotubes with a transmission electron microscope, and then arbitrarily selecting 300 carbon nanotubes from the obtained observation photograph and measuring the outer diameter of each of them.

[0113] The average fiber length of the carbon nanotubes is preferably 0.5 μm or more, more preferably 0.8 μm or more, and even more preferably 1.0 μm or more. The fiber length of the carbon nanotubes is preferably 100 μm or less, and more preferably 20 μm or less. The average fiber length of the carbon nanotubes can be calculated by observing and photographing the carbon nanotubes with a scanning electron microscope, then randomly selecting 300 carbon nanotubes from the obtained observation photograph, and measuring the fiber length of each of them. The average fiber length of the carbon nanotubes in the conductor dispersion is also preferably within the above range.

[0114] The aspect ratio is the fiber length of the carbon nanotube divided by the outer diameter. A representative aspect ratio can be calculated using the average fiber length and the average outer diameter. A conductive material with a higher aspect ratio can provide higher conductivity when formed into an electrode. The aspect ratio of the carbon nanotube is preferably 30 or more, more preferably 50 or more, and even more preferably 80 or more. The aspect ratio of the carbon nanotube is preferably 10,000 or less, more preferably 3,000 or less, and even more preferably 1,000 or less.

[0115] The BET specific surface area of ​​carbon nanotubes is 100m 2 / g or more, and 150m 2 / g or more is more preferable, and 200m 2 The specific surface area of ​​the carbon nanotube is preferably 1200 m / g or more. 2 / g or less, and 2 / g or less is more preferable, and 2 The BET specific surface area of ​​the carbon nanotubes can be measured by the BET method using nitrogen adsorption measurement in accordance with JIS Z 8830.

[0116] The carbon purity of the carbon nanotube is expressed by the content (mass%) of carbon atoms in the carbon nanotube. The carbon purity is preferably 80 mass%, more preferably 90 mass% or more, even more preferably 95 mass% or more, even more preferably 98 mass% or more, and even better 99 mass% or more or 99.5 mass% or more, based on 100 mass% of the carbon nanotube. By setting the carbon purity within the above range, problems such as the formation of dendrites due to impurities and the occurrence of short circuits can be prevented. The carbon purity of the carbon nanotube can be determined by an ICP emission spectrometer according to the method described in the Examples.

[0117] <Carbon black> Carbon black is a fine particle whose main component is carbon, and is produced by controlling various properties through the incomplete combustion of oil or gas. Carbon black has a secondary structure (aggregate) in which primary particles are linked together like beads, and a tertiary structure (agglomerate) in which the secondary structures are further aggregated. The secondary and tertiary structures are collectively called structure. When primary particles are observed under an electron microscope, they appear spherical, but the primary particles are not independent in terms of chemical structure, but are linked to adjacent primary particles in the aggregate by chemical bonds to form a secondary structure. On the other hand, the secondary structures are independent in terms of chemical structure, and are aggregated by intermolecular forces to form a tertiary structure. Therefore, the conductivity inside the secondary structure is higher than the conductivity between the secondary structures, including the contact resistance, and it can be said that deagglomerating the tertiary structure while maintaining the structure of the secondary structure as much as possible is effective in obtaining an electrode with excellent conductivity. The secondary structure is sometimes simply called "structure".

[0118] As the carbon black, various types of carbon black can be used, such as acetylene black, furnace black, hollow carbon black, channel black, thermal black, ketjen black, etc. In addition, carbon black that has been subjected to a commonly used oxidation treatment and carbon black that has been subjected to a graphitization treatment can also be used.

[0119] Oxidation treatment of carbon black is a process in which oxygen-containing polar functional groups, such as phenol groups, quinone groups, carboxyl groups, and carbonyl groups, are directly introduced (covalently bonded) to the carbon black surface by treating the carbon black at high temperatures in air or by secondary treatment with nitric acid, nitrogen dioxide, ozone, etc., and is commonly carried out to improve the dispersibility of carbon black.

[0120] Examples of commercially available carbon black include SuperP-Li (manufactured by TIMCAL), Ketjen Black EC-300J, EC-600JD (manufactured by Lion Corporation), Denka Black, Denka Black Li-400, Li-335 (manufactured by Denka Company, acetylene black), and the like, but are not limited to these, and two or more types may be used in combination.

[0121] The average primary particle size of carbon black is preferably from 10 nm to 1 μm, particularly preferably from 20 nm to 200 nm, and further preferably from 25 nm to 100 nm. The average primary particle diameter of carbon black can be calculated by first observing and photographing the carbon black using a transmission electron microscope, randomly selecting 100 spherical primary carbon black particles from the photograph, and measuring the outer diameter of each of them.

[0122] The BET specific surface area of ​​carbon black is 10m 2 / g or more 1500m 2 / g or less, and 2 / g or more 1000m 2 / g or less is more preferable, and 2 / g or more 850m 2 / g or less is more preferable. When the BET specific surface area is within the above range, an efficient conductive network can be formed with a small amount, and the amount of conductive material in the electrode can be reduced. This increases the degree of freedom in battery design, such as increasing the amount of active material and binder resin. Furthermore, when preparing an electrode slurry, the active material and carbon black are easily combined, making it easier to obtain an electrode film having a homogeneous conductive network in which the active material surface is covered with carbon black, which suppresses the electrolyte decomposition reaction at the interface between the electrolyte and the active material, thereby improving the cycle characteristics of the battery. The BET specific surface area of ​​carbon black can be measured by the BET method described in JIS Z 8830.

[0123] In the conductive material composition, the conductive material may be present in an amount of 0.1 to 30 mass %, 1 to 25 mass %, or 3 to 20 mass % relative to the total mass of the conductive material composition, from the viewpoints of dispersibility and storage stability.

[0124] When carbon nanotubes are used as the conductive material in the conductive material composition, the content of the carbon nanotubes is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, even more preferably 1% by mass or more, and even more preferably 3% by mass or more, based on the total mass of the conductive material composition. The content of the carbon nanotubes is preferably 20% by mass or less, more preferably 10% by mass or less. By setting the content of the carbon nanotubes within the above range, the carbon nanotubes can be present well and stably without causing precipitation or gelation. The content of the carbon nanotubes is preferably appropriately adjusted so that a conductive material composition having appropriate fluidity or viscosity is obtained depending on the BET specific surface area of ​​the carbon nanotubes, the affinity to the liquid medium, the dispersing ability of the dispersant, etc. According to one embodiment, since a nitrile-based polymer is used, the initial dispersibility and the shape retention of the carbon nanotubes are good, and it is possible to include the carbon nanotubes at a higher concentration. For example, the content of carbon nanotubes is preferably in the range of 0.1 to 20 mass% relative to the total mass of the conductive material composition, but may also be 1 to 20 mass%, 3 to 20 mass%, 4 to 20 mass%, 5 to 5 mass%, or 8 to 20 mass%.

[0125] When carbon black is used as the conductive material in the conductive material composition, the content of carbon black is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on the total mass of the conductive material composition. The content of carbon black is preferably 30% by mass or less, more preferably 20% by mass or less. By setting the content of carbon black within the above range, carbon black can be present well and stably without causing precipitation or gelation. The content of carbon black is preferably appropriately adjusted so that a conductive material composition having appropriate fluidity or viscosity is obtained depending on the BET specific surface area of ​​carbon black, affinity for the liquid medium, dispersibility of the dispersant, etc. According to one embodiment, since a nitrile-based polymer is used, the initial dispersibility and shape retention of carbon black are good, and carbon black can be contained at a higher concentration. For example, the carbon black content is preferably in the range of 0.1 to 30 mass% relative to the total mass of the conductive material composition, but may also be 1 to 20 mass%, 5 to 20 mass%, 10 to 20 mass%, 12 to mass%, or 15 to 20 mass%.

[0126] In the conductive material composition, the nitrile polymer may be 0.05 to 5 parts by mass, 0.1 to 1 part by mass, or 0.2 to 0.5 parts by mass relative to 100 parts by mass of the conductive material. According to one embodiment, the use of the nitrile polymer provides good initial dispersion and shape retention of the conductive material. In addition, the nitrile polymer can exert its effect even in a small amount relative to the conductive material. For example, the nitrile polymer is preferably 0.05 to 5 parts by mass relative to 100 parts by mass of the conductive material, but may be 0.05 to 0.5 parts by mass, or 0.05 to 0.2 parts by mass.

[0127] The solid content of the conductive material composition may be 0.1 to 30 mass %, 1 to 25 mass %, or 3 to 20 mass %.

[0128] When the conductive material is dispersed by a disperser that uses collision with media such as a bead mill, or when the conductive material is repeatedly passed through a disperser for a long time, the conductive material may break and produce a short-side carbon material. When a short-side carbon material is produced, the viscosity of the conductive material composition decreases, and the gloss of the coating film obtained by coating and drying the conductive material composition increases, so that the dispersion state seems to be good based on these evaluation results alone. However, short-side carbonaceous matter has high contact resistance and is difficult to form a conductive network, which may deteriorate the resistance of the electrode. According to one embodiment, the use of a nitrile-based polymer provides good initial dispersibility and shape retention of the conductive material. Therefore, a conductive network is easily formed in the electrode film, and the rate characteristics and cycle characteristics of the secondary battery can be improved.

[0129] In one embodiment, the conductive material composition may contain additional optional components as necessary. For example, the conductive material composition may contain, as optional components, dispersants, wetting agents, surfactants, pH adjusters, wetting penetrants, leveling agents, polymer components, and the like, as appropriate, within a range that does not impair the object of the present invention. These optional components can be added at any timing, such as before, during, or after the preparation of the conductive material composition. These optional components may also be added at any timing when preparing the polymer composition. These optional components may also be added at any timing when preparing the slurry composition. These timings may be combined and added stepwise.

[0130] As the dispersant and the polymer component, known ones other than the nitrile polymer can be used. Among them, at least one selected from the group consisting of polyvinylpyrrolidone, polyvinyl alcohol, and polyvinyl acetal is particularly preferable. A polymer in which another substituent is introduced into a part of the above polymer, or a modified polymer may be used. When a dispersant or a polymer component is used, the weight average molecular weight is preferably 30,000 or less, more preferably 20,000 or less, and preferably 3,000 or more. If it is out of the above range, there is a concern that the adsorption of the nitrile polymer and the conductive material is hindered.

[0131] The dispersibility of the conductive material in the conductive material composition can also be evaluated by the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer. With the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer, the particle diameter of the conductive material aggregated particles can be estimated by the distribution of scattered light intensity by the particles. The median diameter (μm) is preferably 0.4 or more. The median diameter (μm) is preferably 5.0 or less, more preferably 2.0 or less. By setting the median diameter (μm) within the above range, a conductive material composition in an appropriate dispersion state can be obtained. If the median diameter (μm) is below the above range, the conductive material is in an aggregated state, and if it exceeds the above range, a large number of finely cut conductive materials are generated, making it difficult to form an efficient conductive network.

[0132] The dispersibility of the conductive material in the conductive material composition can also be evaluated by measuring the gloss (i.e., the intensity of reflected light at an incident angle of 60°) of a coating film obtained by coating on a smooth glass substrate, baking and drying. The better the dispersibility of the light incident on the coating film, the smoother the coating film surface will be, and therefore the gloss will be higher. Conversely, the worse the dispersibility, the lower the gloss will be, as light will be scattered by the unevenness of the coating film surface.

[0133] The gloss of the coating film at 60° is preferably 5 or more, more preferably 20 or more, even more preferably 30 or more, and particularly preferably 40 or more. The gloss of the coating film at 60° is preferably 120 or less, more preferably 110 or less, and even more preferably 100 or less. By setting the gloss in the above range, a conductive material composition in an appropriately dispersed state can be obtained. If the gloss is below the above range, the conductive material will be in an aggregated state, and if the gloss is above the above range, a large amount of finely cut conductive material will be generated, making it difficult to form an efficient conductive network.

[0134] The TI value of the conductive material composition can be calculated by dividing the viscosity (mPa·s) at 60 rpm measured with a Brookfield viscometer by the viscosity (mPa·s) at 6 rpm. The TI value is preferably 1.5 or more and 5.0 or less. In one embodiment, the TI value is more preferably 1.5 or more and less than 3.0. The higher the TI value, the greater the structural viscosity due to entanglement of the conductive material, polymer, and other resin components, or their intermolecular forces, and the lower the TI value, the smaller the structural viscosity. By setting the TI value within the above range, it is possible to suppress entanglement of the conductive material, polymer, and other resin components while allowing these intermolecular forces to act appropriately.

[0135] <Distribution method> The conductive material composition can be produced, for example, by dispersing the polymer composition and the conductive material using a dispersing device to finely disperse them. The dispersion treatment can be a multi-stage treatment of two or more steps by arbitrarily adjusting the timing of addition of the materials to be used.

[0136] Examples of the dispersion device include a kneader, a two-roll mill, a three-roll mill, a planetary mixer, a ball mill, a horizontal sand mill, a vertical sand mill, an annular bead mill, an attritor, a high shear mixer, a high pressure homogenizer, and an ultrasonic homogenizer.

[0137] From the viewpoint of promoting the wetting of the conductive material and dissolving coarse particles, it is more preferable to use a high shear mixer in the initial dispersion step, and then to use a high-pressure homogenizer in order to disperse the conductive material while maintaining its aspect ratio. In addition, by dispersing the conductive material with a high-pressure homogenizer and then dispersing the conductive material with a bead mill, the dispersion state can be made uniform while maintaining the fiber length. Alternatively, since the mixed liquid before dispersion can be prepared to have a lower viscosity by using a polymer composition containing the nitrile polymer of the present disclosure, a uniform dispersion state can be achieved while maintaining the fiber length by dispersing the conductive material with a bead mill first to dissolve the conductive material to a certain level and then dispersing the conductive material with a high-pressure homogenizer. The pressure when using the high-pressure homogenizer is preferably 60 to 150 MPa, more preferably 60 to 120 MPa.

[0138] Dispersion methods using a dispersion device include batch dispersion, pass dispersion, circulation dispersion, etc., and any of these methods may be used, or two or more methods may be combined. Batch dispersion is a method in which dispersion is performed using only the dispersion device body without using piping or the like. It is easy to handle, so it is preferable for small-scale production. Pass dispersion is a dispersion method in which the dispersion device body is equipped with a tank that supplies the dispersion liquid through piping and a tank that receives the dispersion liquid, and the dispersion liquid is passed through the dispersion device body. In addition, circulation dispersion is a method in which the dispersion liquid that has passed through the dispersion device body is returned to the tank that supplies the dispersion liquid, and dispersion is performed while circulating. In either case, the longer the processing time, the more the dispersion progresses, so it is sufficient to repeat the pass or circulation until the desired dispersion state is reached, and the processing amount can be increased by changing the size of the tank or the processing time. Pass dispersion is preferable in that it is easier to homogenize the dispersion state than circulation dispersion. Circulation dispersion is preferable in that the work and manufacturing equipment are simpler than pass dispersion. In the dispersion process, the disintegration of aggregated particles, the loosening, wetting, stabilization, etc. of the conductive material proceed sequentially or simultaneously, and the final dispersion state differs depending on how the processes proceed. Therefore, it is preferable to control the dispersion state in each dispersion process by using various evaluation methods. For example, it can be controlled by the method described in the examples.

[0139] <Slurry Composition> The slurry composition according to one embodiment of the present disclosure includes a polymer composition for electrochemical devices, a conductive material, and an active material. The details of the polymer composition for electrochemical devices and the conductive material are as described above. The active material will be described below.

[0140] The slurry composition may contain a positive electrode active material or a negative electrode active material. In the present disclosure, the positive electrode active material and the negative electrode active material may be simply referred to as "active material". The active material is a material that is the basis of a battery reaction. The active material is divided into a positive electrode active material and a negative electrode active material based on the electromotive force. In the present disclosure, a slurry composition containing a positive electrode active material or a negative electrode active material may be referred to as a "positive electrode slurry composition", a "negative electrode slurry composition", or simply a "slurry composition". The slurry composition is preferably in a slurry form to improve uniformity and processability.

[0141] <Cathode active material> The positive electrode active material is not particularly limited, but for example, for secondary battery applications, metal compounds such as metal oxides and metal sulfides that can reversibly dope or intercalate lithium ions, sodium ions, etc., and conductive polymers can be used. Examples include oxides of transition metals such as Fe, Co, Ni, and Mn, composite oxides with lithium and sodium, inorganic compounds such as transition metal sulfides, polyanion compounds, and Prussian blue. Specific examples include MnO, VO, V 6O13, transition metal oxide powder such as TiO2, composite oxide powder of lithium and transition metal such as lithium nickel oxide, lithium cobalt oxide, lithium manganate, lithium manganate having a spinel structure, lithium iron phosphate-based material which is a phosphoric acid compound having an olivine structure, transition metal sulfide powder such as TiS2, FeS, sodium ferrate, sodium manganate, sodium chromate, sodium nickelate having a layered structure, sodium iron phosphate-based material which is a phosphoric acid compound having an olivine structure, etc. Also, conductive polymers such as polyaniline, polyacetylene, polypyrrole, polythiophene, etc. can be used. Also, the above inorganic compounds and organic compounds may be mixed and used.

[0142] The positive electrode active material is preferably a composite oxide of lithium containing a transition metal such as Al, Fe, Co, Ni, or Mn, more preferably a composite oxide of lithium containing any of Al, Co, Ni, or Mn, and particularly preferably a composite oxide of lithium containing Ni and / or Mn. An active material containing Ni and / or Mn (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more) tends to become highly basic due to the elution of raw material-derived components or metal ions, which tends to cause gelation of the binder or deterioration of the dispersion state, and the problem of the present disclosure may become prominent. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, the embodiment of the present disclosure is particularly effective.

[0143] <Negative electrode active material> The negative electrode active material is not particularly limited as long as it can be doped or intercalated with lithium ions, sodium ions, etc. For example, metal Li or its alloys, alloys such as tin alloys, silicon alloys, and lead alloys, Li X TiO2, Li X Fe2O3, Li X Fe3O4, Li XMetal oxides such as WO2, conductive polymers such as polyacetylene and poly-p-phenylene, highly graphitized carbon materials and other artificial graphite, carbonaceous powders such as natural graphite, and resin-sintered carbon materials can be used. <x<1である。

[0144] These negative electrode active materials can be used alone or in combination. In particular, when a silicon alloy negative electrode is used, the theoretical capacity is large but the volume expansion is extremely large, so it is preferable to use it in combination with artificial graphite such as a highly graphitized carbon material, carbonaceous powder such as natural graphite, resin-sintered carbon material, etc.

[0145] When the conductive material in the slurry composition is carbon nanotubes, the content of carbon nanotubes is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and even more preferably 0.03% by mass or more, based on the mass of the active material (the mass of the active material is 100% by mass). Also, it is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, based on the mass of the active material (the mass of the active material is 100% by mass). Also, it is preferably 20% by mass or less, and more preferably 10% by mass or less. Note that the conductive material may be a combination of carbon nanotubes and carbon black, or two or more of each may be used, but the total amount of each added is preferably within the above range. If it exceeds the above range, the amount of active material filled in the electrode decreases, resulting in a lower capacity battery. If the content is below the above range, the conductivity of the electrode and the battery may be insufficient.

[0146] The content of the nitrile polymer in the slurry composition is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass), and is preferably 10% by mass or less, more preferably 5% by mass or less.

[0147] <Binder resin> The slurry composition may further contain a binder resin. The binder resin used in the slurry composition is a resin capable of binding materials such as active materials and conductive materials. The binder resin is not particularly limited as long as it is usually used as a binder resin for paints, and can be appropriately selected depending on the purpose. That is, in addition to the nitrile polymer, the slurry composition may contain a resin capable of binding materials such as active materials and conductive materials.

[0148] Examples of the binder resin used in the slurry composition include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as constituent units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, fluororesins; cellulose resins such as carboxymethylcellulose (CMC); elastomers such as styrene-butadiene rubber and fluororubber; conductive resins such as polyaniline and polyacetylene, etc. Modified bodies, mixtures, and copolymers of these resins may also be used.

[0149] Among these, the binder resin used in the positive electrode composition is preferably a polymer or copolymer having a fluorine atom in the molecule from the viewpoint of durability. For example, polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene, etc. are preferable. In addition, the binder resin used in the negative electrode composition is preferably carboxymethylcellulose (CMC), styrene butadiene rubber, polyacrylic acid, etc., because of good adhesion.

[0150] The content of the binder resin used in the slurry composition is preferably from 0.5 to 30 mass %, more preferably from 0.5 to 25 mass %, of the non-volatile content of the slurry composition.

[0151] When the slurry composition contains a binder resin, the content of the binder resin in the slurry composition is preferably 0.5% by mass or more, more preferably 0.8% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass), and is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less.

[0152] The solid content in the slurry composition is preferably 30% by mass or more, more preferably 40% by mass or more, based on the mass of the slurry composition (mass of the slurry composition being 100% by mass), and is preferably 90% by mass or less, more preferably 80% by mass or less.

[0153] The slurry composition can be prepared by various conventional methods. For example, a method of preparing the slurry composition by adding an active material to a conductive material composition; a method of preparing the slurry composition by adding an active material to a conductive material composition and then adding a binder resin; a method of preparing the slurry composition by adding a binder resin to a conductive material composition and then adding an active material; a method of preparing the slurry composition by first mixing an active material, a binder resin, and a liquid medium as necessary, and then adding a conductive material composition, etc. are listed. As a method of preparing a slurry composition containing carbon nanotubes as a conductive material, a method of adding a binder resin to a conductive material composition, and then further adding an active material and performing a process of dispersing the mixture is preferable. By preparing the slurry composition by this method, it is possible to prepare the slurry composition without destroying the dispersion state of the carbon nanotubes. The dispersing device used for dispersion is not particularly limited. The slurry composition can be obtained by using the dispersing means mentioned in the explanation of the conductive material composition.

[0154] <Electrode film> The electrode film according to an embodiment of the present disclosure is formed using a slurry composition. Details of the slurry composition are as described above. In addition, an electrode including a current collector and an electrode film formed on the current collector can be provided.

[0155] The electrode film can be obtained, for example, by applying a slurry composition onto a current collector and drying it. An electrode film formed using the positive electrode slurry composition can be used as a positive electrode. An electrode film formed using the negative electrode slurry composition can be used as a negative electrode. In the present disclosure, a film formed using a slurry composition containing an active material may be referred to as an "electrode mixture layer".

[0156] The material and shape of the current collector used to form the electrode film are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. Examples of the material of the current collector include conductive metals or alloys such as aluminum, copper, nickel, titanium, and stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil current collector, and a mesh current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.

[0157] The method of applying the slurry composition onto the current collector is not particularly limited, and any known method can be used.Specific examples of the application method include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.The drying method includes, for example, drying by leaving the composition to dry, or drying using a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, and the like, but is not particularly limited thereto.

[0158] After coating, rolling treatment may be performed using a lithographic press, a calendar roll, etc. The thickness of the formed film is, for example, from 1 μm to 500 μm, and preferably from 10 μm to 300 μm.

[0159] The electrode film formed using the slurry composition can also be used as an underlayer for the electrode mixture layer. By providing such an underlayer, it is possible to improve the adhesion between the electrode mixture layer and the current collector, or to improve the conductivity of the electrode film.

[0160] <Electrochemical element> According to an embodiment of the present disclosure, an electrochemical element can be provided. Suitable electrochemical elements include secondary batteries and capacitors. At least one of the electrode bodies of the electrochemical element may include an electrode film formed using the slurry composition. Details of the slurry composition and the electrode film are as described above. Suitable secondary batteries include lithium ion secondary batteries, alkaline secondary batteries, lead storage batteries, sodium sulfur secondary batteries, and lithium air secondary batteries. The secondary battery is preferably a non-aqueous secondary battery. Suitable capacitors include electric double layer capacitors, lithium ion capacitors, hybrid capacitors, and redox capacitors.

[0161] <Secondary battery> The secondary battery according to an embodiment of the present disclosure includes a positive electrode, a negative electrode, and an electrolyte, and at least one of the positive electrode and the negative electrode includes an electrode film formed using a slurry composition. The details of the slurry composition and the electrode film are as described above.

[0162] As the electrolyte, various conventionally known electrolytes capable of moving ions can be used. For example, the electrolyte may include, but is not limited to, lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group). The electrolyte is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0163] Examples of non-aqueous solvents include, but are not limited to, carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0164] The non-aqueous electrolyte secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.

[0165] The structure of the nonaqueous electrolyte secondary battery of this embodiment is not particularly limited. In one embodiment, the nonaqueous electrolyte secondary battery may generally include a positive electrode and a negative electrode, and a separator that is provided as necessary. The nonaqueous electrolyte secondary battery may be in various shapes such as a paper type, a cylindrical type, a button type, a laminated type, etc., depending on the purpose of use. EXAMPLES

[0166] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, as long as it does not exceed the gist of the present invention. Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". The blending amounts in the table are parts by mass, and the amounts other than the solvent are calculated as non-volatile contents. The blanks in the table indicate that no ingredients are blended.

[0167] The materials used in the examples and comparative examples are shown below. Hydrogenated nitrile butadiene rubber (manufactured by Zannan Scitech, liquid hydrogenated nitrile butadiene rubber, weight average molecular weight 30,000, alkylene structural unit 66% by mass, nitrile group-containing structural unit content 34% by mass), hereinafter referred to as HNBR2. Hydrogenated nitrile butadiene rubber (Zannan Scitech, ZN35052, Mooney viscosity 20, weight average molecular weight 110,000, alkylene structural unit 66% by mass, nitrile group-containing structural unit content 34% by mass), hereinafter referred to as HNBR4. Li-335: Denka Black Li-335 (manufactured by Denka Corporation, acetylene black, average primary particle diameter 23 nm, BET specific surface area 141 m 2 / g, carbon purity 99.9%) or less, CB1. CellSeed NMC (LiNi0.6Co0.2Mn0.2O2, manufactured by Nippon Chemical Industry Co., Ltd., 100% non-volatile content), hereafter referred to as NCM1. S800 (LiNi0.8Mn0.1Co0.1O2, manufactured by Kinwa, non-volatile content 100%), hereafter referred to as NCM2. NAT-7050 (LiNi0.8Co0.15Al0.05O2, manufactured by BASF Toda Battery Materials), hereafter referred to as NCA. HED (trademark) LFP-400 (lithium iron phosphate, manufactured by BASF), hereafter referred to as LFP.

[0168] <cnt1> JENOTUBE10B (manufactured by JEIO, average outer diameter 10nm, BET specific surface area 230m) in a 120L heat-resistant container 2 10 kg of JENOTUBE10B (1000 g / g) was weighed out and the heat-resistant container containing JENOTUBE10B was placed in a furnace. Nitrogen gas was then introduced into the furnace and the air in the furnace was evacuated while maintaining positive pressure. After the oxygen concentration in the furnace fell to 0.1% or less, it was heated to 1600°C over 30 hours. While maintaining the furnace temperature at 1600°C, chlorine gas was introduced at a rate of 50 L / min for 50 hours. Nitrogen gas was then introduced at 50 L / min to cool the material while maintaining positive pressure, yielding purified JENOTUBE10B. The purity was 99.9%. The further purified JENOTUBE10B was fed into a Dynamic Mill (manufactured by Nippon Coke & Co., Ltd.) with zirconia beads of 8 mm diameter as grinding media, and processed under operating conditions of 10.0 kg / h at a peripheral speed of 5.0 m / s to obtain CNT1.

[0169] CNT1 was decomposed with acid using a microwave sample pretreatment device (Milestone General, ETHOS1) to extract the metals contained in the carbon material. Analysis was performed using a multi-type ICP emission spectrometer (Agilent, 720-ES) to calculate the amount of metals (total amount of iron, cobalt, nickel, copper, nickel, and chromium) contained in the extract. The carbon purity of CNT1 was calculated as follows and was 99.9%. Carbon purity (%) = ((carbon material mass - metal amount) ÷ carbon material mass) × 100

[0170] <cnt2> A 120L heat-resistant container was filled with JENOTUBE6A (manufactured by JEIO, average outer diameter 6 nm, BET specific surface area 650 m 2 10 kg of JENOTUBE6A (CNT2) was weighed out and the heat-resistant container containing JENOTUBE6A was placed in a furnace. Nitrogen gas was then introduced into the furnace and the air inside the furnace was evacuated while maintaining positive pressure. After the oxygen concentration inside the furnace fell to 0.1% or less, it was heated to 1600°C over 30 hours. While maintaining the furnace temperature at 1600°C, chlorine gas was introduced at a rate of 50 L / min for 50 hours. Nitrogen gas was then introduced at 50 L / min to cool the furnace while maintaining positive pressure, yielding purified JENOTUBE6A (CNT2).

[0171] CNT2 was decomposed with acid using a microwave sample pretreatment device (Milestone General, ETHOS1) to extract the metals contained in the carbon material. After that, analysis was performed using a multi-type ICP emission spectrometer (Agilent, 720-ES) to calculate the amount of metals (total amount of iron, cobalt, nickel, copper, nickel, and chromium) contained in the extract. The carbon purity of CNT2 was 99.9%.

[0172] <lfmp> LFMP is synthesized by the following synthesis procedure. 200 g of dimethyl sulfoxide is added to 150 g of pure water, and 360 mmol of lithium hydroxide monohydrate is added. 120 mmol of phosphoric acid is further added to the resulting solution using an 85 wt% aqueous phosphoric acid solution, and 96 mmol of manganese (II) sulfate monohydrate and 24 mmol of iron (II) sulfate heptahydrate are further added. The resulting solution is transferred to an autoclave and heated to maintain the temperature inside the container at 150°C for 4 hours. After heating, the supernatant of the solution is discarded, and lithium iron manganese phosphate LiMn is collected as a precipitate. 0.8 Fe 0.2 PO4 is obtained. After washing the obtained lithium manganese iron phosphate with pure water, the operation of removing the supernatant by centrifugation is repeated five times, and finally pure water is added again to obtain a dispersion liquid. Next, glucose of the same weight as 15% by weight of the lithium manganese iron phosphate in the dispersion liquid is added and dissolved in the dispersion liquid, and then pure water is added to adjust the solid concentration of the dispersion liquid to 20% by weight, thereby obtaining an LFMP dispersion liquid. The obtained LFMP dispersion liquid is dried with hot air at 200 ° C using a spray dryer (manufactured by Fujisaki Electric Co., Ltd., MDL-050B) to obtain secondary particles. The obtained secondary particles are heated at 700 ° C for 4 hours in a nitrogen atmosphere using a rotary kiln to obtain carbon-coated LFMP particles (hereinafter referred to as LFMP).

[0173] <Polymer Composition> [Synthesis of HNBR1] HNBR1 is synthesized by the following synthesis procedure. 500 g of monochlorobenzene is placed in a 1 L autoclave equipped with a stirrer, and 75 g of nitrile rubber (Perbunan® 3430: content of nitrile group-containing units 34%, Mooney viscosity 32) finely chopped with a rubber chopper is added and dissolved while stirring. After the nitrile rubber is completely dissolved, 4 phr of 1-hexene is added to the vessel, and the solution is stirred for 2 hours, during which the catalyst 1,3-bis-(2,4,6-trimethylphenyl)-2-imidazolidinylidene)(tricyclohexylphosphine)-ruthenium(phenyl-methylene)dichloride is dissolved in 20 mL of monochlorobenzene and added to the vessel. The reaction mixture is reacted for 12 hours with stirring at a temperature of 22°C. After the reaction, a monochlorobenzene solution of tris-(triphenylphosphine)rhodium chloride (0.06 phr) is charged into the reactor, and the reactor is pressurized with hydrogen to 85 bar. The reaction mixture is reacted at a temperature of 135°C for 4 hours with stirring (500 rpm) to obtain a polymer solution. After concentrating to a certain extent using a rotary evaporator, the solution is poured into a stainless steel tray and dried in an exhaust-type heating oven heated to 140°C until the odor of monochlorobenzene disappears, to obtain HNBR1. 1 The structural unit derived from acrylonitrile was determined to be 34% from the H-NMR quantitative spectrum.

[0174] [Preparation of HNBR3] 92 parts by mass of NMP was placed in a stainless steel container, and stirred with a disperser while heating the liquid temperature to 80°C. 8 parts by mass of HNBR2, which had been heated to 80°C in a separate container, was added to NMP and stirred for 1 hour to prepare a polymer solution. 1000 parts by mass of methanol was placed in another stainless steel container, and while stirring at room temperature (25°C), the polymer solution previously prepared was dropped to coagulate, decanted, and dried in an exhaust type heating oven heated to 140°C. The above steps (preparation of polymer solution, coagulation with methanol, decantation, drying) were repeated three times to obtain HNBR3. 1 The structural unit derived from acrylonitrile was determined to be 34% from the H-NMR quantitative spectrum.

[0175] [Preparation of HNBR5] In an autoclave equipped with a stirrer, 240 parts of ion-exchanged water, 2.5 parts of sodium alkylbenzenesulfonate as an emulsifier, 35 parts of acrylonitrile as a nitrile group-containing monomer, and 0.85 parts of t-dodecyl mercaptan as a chain transfer agent were placed in this order, and the inside was replaced with nitrogen, after which 65 parts of 1,3-butadiene as a conjugated diene monomer was pressed in, and 0.25 parts of ammonium persulfate as a polymerization initiator was added, and polymerization reaction was carried out at a reaction temperature of 40°C. Then, a polymer of acrylonitrile and 1,3-butadiene was obtained. The polymerization conversion rate was 85%.

[0176] Ion-exchanged water was added to the obtained copolymer to obtain a solution with a total solid concentration adjusted to 12% by mass. 400 mL of the obtained solution (total solid content 48 g) was placed in a 1 L autoclave equipped with a stirrer, and nitrogen gas was passed through for 10 minutes to remove dissolved oxygen in the solution. 75 mg of palladium acetate as a catalyst for hydrogenation reaction was dissolved in 180 mL of ion-exchanged water to which 4 times the molar amount of nitric acid relative to palladium (Pd) was added, and the system was replaced twice with hydrogen gas, and the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3 MPa, and the hydrogenation reaction was carried out for 6 hours.

[0177] Next, the autoclave was returned to atmospheric pressure, and 25 mg of palladium acetate as a hydrogenation catalyst was dissolved in 60 mL of ion-exchanged water containing 4 times the molar amount of nitric acid relative to Pd, and added. After replacing the inside of the system with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3 MPa, and the hydrogenation reaction was carried out for 6 hours. Thereafter, the contents were returned to room temperature, the inside of the system was conditioned with nitrogen, and the contents were concentrated using an evaporator until the solid content reached 40%, to obtain an aqueous dispersion of the polymer.

[0178] Furthermore, the aqueous dispersion of the polymer was dropped into methanol to coagulate the polymer, and the coagulated product was then vacuum dried at 60° C. for 12 hours to obtain HNBR5. 1 The content of structural units derived from acrylonitrile as determined from the H-NMR quantitative spectrum was 35%, and the Mooney viscosity (ML1+4, 100°C) was 10.

[0179] [Preparation of polymer composition] (Polymer Composition 1) A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 800 parts by mass of NMP and substituted with nitrogen gas. Then, the reaction vessel was heated to 80° C., 200 parts of HNBR1 was added, and the mixture was stirred until HNBR1 was completely dissolved, to obtain a polymer composition 1 (solid content concentration 20% by mass).

[0180] (Polymer Compositions 2-3) Polymer compositions 2 and 3 were obtained in the same manner as for polymer composition 1, except that the polymer to be dissolved was changed to one shown in Table 1.

[0181] (Polymer Composition 4) Capacity 1000cm 3 475 parts by mass of NMP and 25 parts by mass of NaOH (Tosoh Pearl, manufactured by Tosoh Corporation) were added to a plastic container, and the mixture was dispersed uniformly at a speed of 9000 rpm using a high-shear mixer (L5M-A, manufactured by Silverson) equipped with a fine emulsion screen. The mixture was then passed through a nylon filter with 150 μm openings using a filtration bell to produce a NaOH dispersion (NaOH concentration 5% by mass).

[0182] A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 780 parts by mass of NMP and substituted with nitrogen gas. Then, the reaction vessel was heated to 80°C, 2200 parts of HNBR was added, and the mixture was stirred until the hydrogenated nitrile butadiene rubber was completely dissolved. Then, 20 parts by mass of NaOH dispersion was added, and the mixture was stirred while adding air, and the reaction vessel was heated at 80°C for 12 hours to obtain a polymer composition 4 (solid content concentration 20.1% by mass).

[0183] (Polymer Compositions 5 to 9) Polymer compositions 5 to 9 were obtained in the same manner as polymer composition 4, except that the type and amount of base added were changed as shown in Table 1.

[0184] (Comparative polymer composition 1) In a reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer, 800 parts by mass of NMP was charged and replaced with nitrogen gas. Then, the reaction vessel was heated to 80°C, 200 parts of HNBR4 was added, and the mixture was stirred until the hydrogenated nitrile butadiene rubber was completely dissolved, to obtain a comparative polymer composition 1 (solid content concentration 20% by mass).

[0185] (Comparative polymer composition 2) Capacity 1000cm 3 475 parts by mass of NMP and 25 parts by mass of NaOH (Tosoh Pearl, manufactured by Tosoh Corporation) were added to a plastic container, and the mixture was dispersed uniformly at a speed of 9000 rpm using a high-shear mixer (L5M-A, manufactured by Silverson) equipped with a fine emulsion screen. The mixture was then passed through a nylon filter with 150 μm openings using a filtration bell to produce a NaOH dispersion.

[0186] A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 780 parts by mass of NMP and substituted with nitrogen gas. Then, the reaction vessel was heated to 80°C, 200 parts of HNBR4 was added, and the mixture was stirred until the hydrogenated nitrile butadiene rubber was completely dissolved. Then, 20 parts by mass of NaOH dispersion was added, and the mixture was stirred while adding air, and the reaction vessel was heated at 80°C for 12 hours to obtain a comparative polymer composition 2 (solid content concentration 20.1% by mass).

[0187] (Comparative polymer composition 3) In a reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer, 800 parts by mass of NMP was charged and replaced with nitrogen gas. Then, the reaction vessel was heated to 80°C, 200 parts of HNBR5 was added, and the mixture was stirred until the hydrogenated nitrile butadiene rubber was completely dissolved, to obtain a comparative polymer composition 3 (solid content concentration 20% by mass).

[0188] For Examples 1-3, 1-6, and Comparative Example 1-1, a chart of tan δ (loss tangent) for evaluating the strain dependency of the polymer composition is shown in Figure 1. For Examples 1-3, 1-6, 1-7, and Comparative Example 1-1, a chart of tan δ (loss tangent) for evaluating the temperature dependency of the polymer composition is shown in Figure 2.

[0189] <<Physical property measurement and evaluation methods>> The methods for measuring and evaluating the physical properties of the polymer compositions, conductive material compositions, electrode films, and secondary batteries used in the examples and comparative examples described below are as follows.

[0190] <Preparation of molecular weight measurement sample> The polymer composition was dropped into purified water to precipitate the polymer, and the precipitate was collected by filtration using a Buchner funnel. The precipitate was rinsed by sprinkling purified water on the Buchner funnel as it was, and then dissolved in tetrahydrofuran (THF) to obtain a solution. The obtained solution was dropped again into purified water to carry out the filtration and washing steps using purified water, and the precipitate was redissolved in THF to obtain a molecular weight measurement sample.

[0191] <Measurement of weight average molecular weight (Mw) and Z average molecular weight (Mz)> The weight-average molecular weight (Mw) and Z-average molecular weight (Mz) of the polymer composition were measured by gel permeation chromatography (GPC) equipped with an RI detector using a molecular weight measurement sample. An HLC-8320GPC (manufactured by Tosoh Corporation) was used as the apparatus, and three separation columns were connected in series, with Tosoh Corporation's "TSK-GEL SUPER AW-4000", "AW-3000", and "AW-2500" used as the packing materials, in that order, at an oven temperature of 40°C, an N,N-dimethylformamide solution of 30 mM triethylamine and 10 mM LiBr as the eluent, and a flow rate of 0.6 mL / min. The concentration of the measurement sample was adjusted to 1% using a solvent consisting of the eluent, and 20 microliters were injected. The weight-average molecular weight and Z-average molecular weight are polystyrene equivalent values. The weight average molecular weight (Mw) was rated as follows: A for 70,000 or less, B for more than 70,000 to 100,000, and C for over 100,000.

[0192] <Preparation of a solution with a solid content of 20% by mass> 80 parts by mass of NMP was placed in a stainless steel container, and stirred with a disperser while heating to a liquid temperature of 80° C. A polymer heated to 80° C. in a separate container was added to NMP so that the polymer concentration was 20% by mass, and after stirring for 1 hour, it was confirmed with a spoon or the like that there was no undissolved polymer on the liquid surface, container wall, or bottom, and the solid content was measured and corrected with NMP to a solid content of 20% by mass, thereby preparing a polymer solution.

[0193] <Viscosity measurement of a solution with a solid content of 20% by mass> The prepared polymer solution was allowed to stand in a thermostatic bath at 25° C. for 1 hour or more, and the viscosity was immediately measured using a B-type viscometer at a rotor rotation speed of 60 rpm. The viscosity was rated as follows: less than 500 mPa·s was rated A, between 500 and 1000 mPa·s was rated B, between 1000 and 3000 mPa·s was rated C, and over 3000 mPa·s was rated D.

[0194] <Measurement of Viscoelasticity of Polymer Composition> (Preparation of sample pieces) A fluororesin mold was cut out to fit a measuring tool (parallel plate diameter 25 mm), the polymer composition was dropped onto the fluororesin mold, and the fluororesin mold was dried in an oven at 140°C for 1 hour to remove the solvent and prepare a sample piece. The polymer composition of the example was viscous and could not be separated from the fluororesin mold as it was, so it was cooled with liquid nitrogen and solidified before being removed from the fluororesin mold. A plate was heated to 80°C so that the thickness of the sample was constant, and the sample piece was placed on it, and the thickness was corrected with the measuring tool. It was also confirmed that the prepared sample piece did not contain any bubbles.

[0195] (Dynamic viscoelasticity test: strain dependency evaluation) The dynamic viscoelasticity (strain dependency) of the polymer was measured using a viscoelasticity measuring device: MCR302e (Anton Paar). Specifically, using parallel plates with a diameter of 25 mm, the GAP was set to the thickness of the sample, and measurements were performed under the conditions of a temperature of 100°C, a frequency of 10 Hz, and a strain of 0.01 to 10%. The strain dependency of the polymer was evaluated using a chart of horizontal axis strain vs. vertical axis tan δ (loss tangent). Here, tan δ (loss tangent) is calculated as: loss modulus (G'') / storage modulus (G').

[0196] (Dynamic viscoelasticity test: temperature dependency evaluation) The dynamic viscoelasticity (temperature dependence) of the polymer was measured using a viscoelasticity measuring device: MCR302e (Anton Paar). Specifically, using a 25 mm diameter parallel plate, the measurements were performed under the following conditions: normal force constant 100 mN, frequency 10 Hz, strain 0.1%, temperature range 30°C to 110°C, and temperature drop rate 10°C / min. The temperature dependence of the polymer can be evaluated by reading the temperature at which tanδ (loss tangent) = 1 from a chart of temperature on the horizontal axis vs. tanδ (loss tangent) on the vertical axis. A was assigned to 40°C to 80°C, B to 30°C to 40°C or to 80°C to 110°C, C to less than 30°C, and D to more than 110°C.

[0197] (Method for measuring Mooney viscosity of polymers (ML1+4, 100℃)) Purified water was dropped into the polymer composition to coagulate the polymer. The coagulated product was collected, washed with methanol, transferred to a petri dish, and vacuum-dried at 60°C for 12 hours to obtain 40 g of a flat plate sample for measurement. The Mooney viscosity (ML1+4, 100°C) was measured at a temperature of 100°C using an L-shaped rotor in accordance with the Japanese Industrial Standard JIS K6300-1.

[0198] <Evaluation of Dispersibility of Polymer Composition> 80 parts by mass of NMP was placed in a stainless steel container, and stirred with a disperser while heating the liquid temperature to 80° C. A polymer heated to 80° C. in a separate container was added to NMP so that the polymer concentration was 8% by mass, and after stirring for 1 hour, it was confirmed with a spoon or the like that there was no undissolved polymer on the liquid surface, container wall, or bottom, and the solid content was measured and corrected with NMP to make the solid content 8% by mass, thereby preparing polymer solution X.

[0199] 98 parts by mass of the prepared polymer solution X was placed in a glass container, and carbon nanotubes JENOTUBE10B (average outer diameter 10 nm, BET specific surface area 230 m 2 Two parts by mass of the glass container (10% height from the top of the glass container, multi-walled CNTs) were added and left to stand for one hour without stirring. After that, samples were collected from the supernatant (10% height from the top of the glass container) and the bottom (10% height from the bottom of the glass container). The amount dropped onto the tared aluminum dish (W1) was then measured using a precision balance. The measured mass was recorded as W2. The aluminum dish was then dried in an oven at 140°C for one hour, and the mass of the aluminum dish was measured again using the precision balance (W3). The solid content of the supernatant and bottom was calculated using the following formula 2. Solid content = (W3-W1) / W2 Equation 2

[0200] The dispersibility of the polymer composition was then evaluated from the dispersion degree of the carbon nanotubes, calculated by dividing the solid content of the supernatant by the solid content of the bottom. A was given for 0.75 or more but less than 1.25, B for 0.5 or more but less than 0.75 or 1.25 or more but less than 1.50, and C for less than 0.5 or 1.50 or more.

[0201] <Initial Viscosity of Conductive Composition> The conductive material composition was left to stand in a thermostatic chamber at 25°C for at least one hour, and then immediately measured using a Brookfield viscometer with a rotor rotation speed of 100 rpm. The initial viscosity was evaluated as follows: A for 100 mPa·s or more but less than 500 mPa·s, B for 500 mPa·s or more but less than 1000 mPa·s, C for 1000 mPa·s or more but less than 2000 mPa·s, and D for over 2000 mPa·s.

[0202] <Evaluation of dispersibility of conductive composition> The dispersibility of the conductive material composition was evaluated by measuring the cumulative particle diameter D50. The cumulative particle diameter D50 was measured by particle size distribution using a laser diffraction / scattering type particle size distribution measuring device (Horiba, Ltd.; Partical LA-960V2). The laser light wavelength of this measuring device is 650 nm, and the detectors include one ring-shaped 64-segment silicon photodiode, five 4-channel array detectors, and three silicon photodetectors. In addition, the measuring section uses a flow-type cell (sample cell) made of synthetic quartz. First, NMP, which is the same solvent as the dispersion liquid, was put into a sample bath containing a sample cell, and circulation / ultrasonic cleaning was performed. The operation modes were circulation speed: 3, ultrasonic intensity: 7, ultrasonic time: 1 minute, stirring speed: 7, and stirring mode: continuous. Next, in order to remove air, ultrasonic operation was performed at ultrasonic intensity: 7 and ultrasonic time: 5 seconds, and then a blank (background) measurement was performed. The particle size standard was set to volume, the particle refractive index was set to 1.920-0.522i (carbon material), and the solvent refractive index was set to 1.468 (NMP). The dispersion liquid was dropped so that the laser light transmittance during measurement was 60% ± 1%, and sample adjustment was performed. The operation modes during measurement were circulation speed: 3, stirring speed: 7, and stirring mode: continuous, and the measurement was performed. The dispersibility of the conductive material composition was evaluated as follows: A: cumulative particle size D50 value less than 3 μm; B: 3 μm or more and less than 10 μm; and C: 10 μm or more.

[0203] <Evaluation of storage stability of conductive composition> The conductive material composition was left to stand in a thermostatic chamber at 40° C. for one week, and then cooled to 25° C., and immediately measured for viscosity over time using a B-type viscometer with a rotor rotation speed of 100 rpm. The storage stability was evaluated by dividing the viscosity over time (after one week at 40° C.) by the initial viscosity, with A being 0.8 or more and less than 3.0, B being 3.0 or more and less than 5.0, and C being less than 0.8 or 5.0 or more.

[0204] <Adhesion evaluation of electrode film> The adhesion of the electrode film was evaluated by measuring the peel strength. The composite slurry was applied to the electrode using an applicator so that the coating weight per unit area of ​​the electrode was 20 mg / cm. 2 After coating on aluminum foil so that the coating was as above, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes. Then, the film was cut into two 90mm x 20mm rectangles with the coating direction as the long axis. Peel strength was measured using a tabletop tensile tester (Strograph E3, manufactured by Toyo Seiki Seisakusho Co., Ltd.) and evaluated by a 180-degree peel test method. Specifically, a double-sided tape (No. 5000NS, manufactured by Nitoms Co., Ltd.) measuring 100mm x 30mm was attached to a stainless steel plate, the prepared battery electrode composite layer was attached to the other side of the double-sided tape, and the layer was peeled off while being pulled from the bottom to the top at a constant speed (50mm / min). The average value of the stress at this time was taken as the peel strength. The adhesion of the electrode film was evaluated as follows: A for a peel strength of 1.0 N / cm or more, B for a peel strength of 0.7 N / cm or more but less than 1.0 N / cm, C for a peel strength of 0.5 N / cm or more but less than 0.7 N / cm, and D for a peel strength less than 0.5 N / cm.

[0205] <Evaluation of rate characteristics of lithium-ion secondary batteries> The laminated lithium-ion secondary battery was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cut-off current 1.0mA (0.02C)) was performed at a charge current of 10mA (0.2C) and a charge end voltage of 4.2V, constant current discharging was performed at a discharge current of 10mA (0.2C) and a discharge end voltage of 2.5V. After repeating this operation three times, constant current / constant voltage charging (cut-off current (1.0mA0.02C)) was performed at a charge current of 10mA (0.2C) and a charge end voltage of 4.2V, and constant current discharging was performed at discharge currents of 0.2C and 3C until the discharge end voltage of 2.5V was reached, and the discharge capacity was calculated for each. The rate characteristic can be expressed as the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 3. Rate characteristic = 3C discharge capacity / 3rd 0.2C discharge capacity × 100 (%) Formula 3 The rate characteristic evaluation was as follows: A for rate characteristics of 80% or more, B for 70% or more but less than 80%, C for 60% or more but less than 70%, and D for less than 60%.

[0206] <Evaluation of high-temperature cycle characteristics of lithium-ion secondary batteries> The laminated lithium-ion secondary battery was placed in a thermostatic chamber at 45°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant-current constant-voltage charging (cutoff current 1.25mA (0.025C)) was performed with a charge current of 50mA (1C) and a charge end voltage of 4.2V, constant-current discharging was performed with a discharge current of 50mA (1C) and a discharge end voltage of 2.5V. This operation was repeated 200 times. 1C was the current value at which the theoretical capacity of the positive electrode was discharged in 1 hour. The cycle characteristics can be expressed by the following formula 4, which is the ratio of the 100th 1C discharge capacity at 45°C to the 3rd 1C discharge capacity. The high-temperature cycle characteristics evaluation was performed with A for cycle characteristics of 90% or more, B for 85% or more but less than 90%, C for 80% or more but less than 85%, and D for less than 80%. High temperature cycle characteristic = 100th 1C discharge capacity / 3rd 1C discharge capacity × 100 (%) Formula 4

[0207] (Example 2-1) In a stainless steel container, 84.0 parts of N-methyl-2-pyrrolidone (NMP) and 8.0 parts of a polymer composition (solid content concentration 20% by mass) were added and stirred using a disperser. Then, 8 parts of CNT1 were taken and added while stirring with a disperser. A fine emulsion screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON), and the mixture was dispersed in a batch manner at a speed of 9000 rpm until the entire mixture became uniform and the dispersion particle size was 200 μm or less using a grind gauge. Then, the mixture was passed through a high magnetic force mag filter (manufactured by Eishin, surface magnetic flux density 17000 Gauss) to prepare a carbon material pre-dispersion composition. After that, the carbon material pre-dispersion composition was sent and subjected to a circulation dispersion treatment (beads filling rate 80%, peripheral speed 13 m / s) with a residence time of 15 minutes using a bead mill (manufactured by Ashizawa Finetech Co., Ltd., Mugen Flow (registered trademark)) filled with zirconia beads having a diameter of 1.0 mm. The number of circulations was 30. Next, the liquid to be dispersed was supplied to a high-pressure homogenizer (Starburst Lab, manufactured by Sugino Machine Co., Ltd.) and a 24-pass dispersion treatment was performed. The dispersion treatment was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa, and then the liquid to be dispersed was supplied to an electromagnet (EMF-100S, manufactured by Taiho Magnetic Co., Ltd., magnetic flux density 16000 Gauss, space volume 1.7 L, diameter: 10 cm, electromagnet equipped with 31 grid screens with a thickness of 1.3 cm) and a three-pass treatment was performed, and then the liquid was passed through two depth filters (NT-T series, PP nonwoven fabric depth cartridge, manufactured by 3M, filtration accuracy 40 μm) installed in series to prepare a conductive material composition 1.

[0208] (Examples 2-2 to 2-12, Comparative Examples 2-1 to 2-3) Conductive compositions were prepared in the same manner as in Example 1 according to the compositions in Table 2, and conductive compositions 2 to 12 and comparative conductive compositions 1 to 3 were prepared.

[0209] (Example 3-1) Capacity 150cm 3 Into the plastic container, 18.8 parts by mass of an NMP solution in which 8% by mass of PVdF (polyvinylidene fluoride, Solvey, Solef#5130) was dissolved, and 14.5 parts by mass of NMP were weighed. Then, 18.8 parts by mass of a conductive material composition (conductive material composition 1) was added, and the mixture was stirred at 2000 rpm for 30 seconds using a rotation-revolution mixer (Awatori Rentaro, ARE-310). Then, 96.7 parts by mass of a positive electrode active material NCM1 was added, and the mixture was stirred at 2000 rpm for 2.5 minutes using a rotation-revolution mixer (Awatori Rentaro, ARE-310) to obtain a composite slurry.

[0210] Next, the composite slurry was applied to the electrode using an applicator so that the weight per unit area of ​​the electrode was 20 mg / cm2. 2 After coating on an aluminum foil so that the coating was as follows: the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain an electrode film (electrode film 1). The electrode film (electrode film 1) was then rolled using a roll press (3t hydraulic roll press, manufactured by Sun Metals) to obtain a positive electrode (positive electrode 1). The weight per unit area of ​​the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling was 3.1 g / cc.

[0211] (Examples 3-2 to 3-16, Comparative Examples 3-1 to 3-3) Positive electrodes (positive electrode 2) to (comparative positive electrode 3) were produced in the same manner as in the production of the positive electrode (positive electrode 1), except that the positive electrode active material and conductive material composition were changed as shown in Table 3.

[0212] (Example 4-1) The positive electrode (positive electrode 1) and the standard negative electrode were punched out to 45 mm x 40 mm and 50 mm x 45 mm, respectively, and the separator (porous polypropylene film) between them was inserted into an aluminum laminate bag and dried in an electric oven at 60°C for 1 hour. After that, in a glove box filled with argon gas, 2 mL of electrolyte (a non-aqueous electrolyte prepared by mixing ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a ratio of 1:1:1 (volume ratio) and adding 2 parts by mass of VC (vinylene carbonate) as an additive to 100 parts by mass of the mixed solvent, and then dissolving LiPF6 at a concentration of 1M) was injected, and the aluminum laminate was sealed to prepare a laminated lithium-ion secondary battery (battery 1).

[0213] (Examples 4-2 to 4-16, Comparative Examples 4-1 to 4-3) Laminated lithium ion secondary batteries (Battery 2) to (Comparative Battery 3) were produced in the same manner as in the production of the laminated lithium ion secondary battery (Secondary Battery 1), except that the positive electrode was changed as shown in Table 4.

[0214] [Table 1]

[0215] [Table 2]

[0216] [Table 3]

[0217] [Table 4] < / lfmp>

Claims

1. A polymer composition for an electrochemical element, comprising: a polymer containing an aliphatic hydrocarbon unit and a nitrile group-containing unit; and an amide-based liquid medium, wherein the polymer has a tan δ (loss tangent) of greater than 1 in a strain range of 0.01% to 10% in a dynamic viscoelastic measurement performed at a temperature of 100° C. and a frequency of 10 Hz, and the content of the aliphatic hydrocarbon unit is 50% by mass or more and 75% by mass or less, and the content of the nitrile group-containing unit is 25% by mass or more and 50% by mass or less, based on the mass of the polymer.

2. The polymer composition for electrochemical elements described in claim 1, wherein the polymer has been given viscosity or fluidity.

3. The polymer composition for electrochemical elements according to claim 1 or 2, wherein the Z-average molecular weight of the polymer is 100,000 or less.

4. 3. The polymer composition for electrochemical elements according to claim 1 or 2, wherein, in a viscoelasticity measurement performed at a frequency of 10 Hz and a strain of 0.1%, the polymer has a measurement temperature at which tan δ (loss tangent) = 1 when heated at a temperature range of 30°C to 110°C at a rate of 10°C / min of 80°C or lower.

5. 3. The polymer composition for electrochemical elements according to claim 1, wherein a solution containing the polymer and N-methyl-2-pyrrolidone and having a solid content concentration of 20% by mass has a viscosity of less than 3000 mPa s at 25° C. and 60 rpm when measured with a B-type viscometer.

6. 3. The polymer composition for electrochemical devices according to claim 1, wherein the Z-average molecular weight of the polymer is 10,000 or more and 250,000 or less.

7. A conductive material composition comprising the polymer composition for electrochemical devices according to claim 1 or 2 and a conductive material.

8. A slurry composition comprising the polymer composition for electrochemical devices according to claim 1 or 2, a conductive material, and an active material.

9. 3. An electrode film formed by using a slurry composition containing the polymer composition for electrochemical devices according to claim 1, a conductive material, and an active material.

10. The battery includes a positive electrode, a negative electrode, and an electrolyte, and at least one of the positive electrode and the negative electrode is 3. A secondary battery comprising an electrode film formed using a slurry composition containing the polymer composition for electrochemical devices according to claim 1, a conductive material, and an active material.

Citation Information

Patent Citations

  • Dispersant, conductive material dispersion, and slurry for electrode film

    JP2021122751A

  • Binder composition for electrochemical element, conductive material dispersion for electrochemical element, slurry for electrochemical element electrode, electrode for electrochemical element, and electrochemical element

    JP2022041234A

  • Binder composition for secondary battery electrodes, conductive material paste composition for secondary battery electrodes, slurry composition for secondary battery electrodes, electrode for secondary batteries, and secondary battery

    WO2017010093A1

  • Cathode slurry composition, and lithium secondary battery manufactured using same

    WO2023121315A1